Oxygen-absorbing coated laminate
The laminate structure with an oxygen-absorbing coat layer addresses the challenge of effective oxygen and water vapor barriers, reducing odor and moisture, and minimizing waste by integrating oxygen absorption into the packaging material.
Patent Information
- Application Number
- JP2020116472
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-07-06
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-07-06
AI Technical Summary
Existing packaging materials struggle to provide effective oxygen and water vapor barriers while maintaining low odor and moisture levels, leading to quality deterioration of contents and increased waste due to the use of oxygen absorbers.
A laminate structure comprising a base layer, an oxygen barrier layer, and an oxygen-absorbing coat layer, where the oxygen-absorbing coat layer contains an oxygen-absorbing compound with unsaturated five-membered rings and an oxidation-promoting catalyst, enhancing oxygen absorption and reducing odor.
The laminate effectively reduces oxygen concentration, suppresses content deterioration, and minimizes waste by eliminating the need for separate oxygen absorbers, while maintaining low odor and moisture levels.
Smart Images

Figure 0007600552000024 
Figure 0007600552000025 
Figure 0007600552000026
Abstract
Description
[Technical field]
[0001] The present invention relates to an oxygen-absorbing coated laminate which generates little odor, has barrier properties against external oxygen gas and water vapor, and absorbs oxygen within a content storage space to suppress oxygen-induced deterioration of the contents, has an excellent balance between aroma retention and blocking resistance, and is suitable for filling packaging, and also relates to an oxygen-absorbing coated packaging material and an oxygen-absorbing coated package made from the oxygen-absorbing coated laminate. [Background technology]
[0002] Conventional packaging methods for preventing the deterioration of the quality of contents, such as food, medical products, chemical products, and cosmetics, due to oxygen have included using packaging materials with high oxygen barrier properties, replacing the gas in the content storage area with an inert gas such as nitrogen gas, and including an oxygen scavenger packaged with reduced iron powder or the like. However, these have problems such as insufficient performance, increased packaging costs, increased waste, only functioning in moist environments, and the risk of accidental ingestion. Furthermore, Patent Document 1 describes a packaging material that uses a resin that has oxygen absorbing properties and emits little odor. However, this resin is polycyclododecene, which is insoluble in polar solvents and has no active hydrogen groups, and is therefore unsuitable as an adhesive raw material for packaging materials made of laminates. Furthermore, Patent Document 2 describes a resin composition made of a resin using methyltetrahydrophthalic acid as a raw material having oxygen absorbing properties, but this composition has the drawback of being unstable and having low oxygen absorbing properties. Patent Document 3 describes an oxygen-absorbing resin that is a thermoplastic resin having a repeating unit composed of a saturated five-membered ring having a substituent that contains a carbon-carbon double bond and a -CH=CH- group linking the saturated five-membered rings. However, this resin has drawbacks such as being difficult to use due to its poor solubility in solvents and emitting a strong odor. Disclosed gas barrier packaging materials containing a paper base material include those having a gas barrier layer made of a water-soluble polymer and an inorganic layered compound on a paper base material (hereinafter also referred to as "base paper") (Patent Documents 4 and 5), and those having a barrier layer made of a specific vinyl alcohol-based polymer on a coating layer (Patent Documents 5 and 6). Disclosed water vapor barrier packaging materials containing a paper base material include packaging paper having a moisture-proof layer made of synthetic resin latex, wax, and inorganic fine particles (Patent Document 7). However, packaging materials in which a resin with gas barrier properties and a resin with water vapor barrier properties are laminated or pasted onto a paper base material (base paper) have limitations on the types of resin that can be laminated, and therefore have the problem of being unable to meet various quality requirements. On the other hand, packaging materials that have been given gas barrier and water vapor barrier properties by coating a paper substrate (base paper) with a resin having gas barrier properties and a resin having water vapor barrier properties have few restrictions on the types of resins that can be used, making it possible to meet various quality requirements. However, when a moisture-proof layer of Patent Document 7 is provided on a packaging material that has both gas barrier and water vapor barrier properties, for example, a packaging material having gas barrier properties of Patent Document 4 or Patent Document 5, there is a problem that good water vapor barrier properties are obtained but gas barrier properties are not obtained. Also, even when a gas barrier layer of Patent Document 4 or Patent Document 5 is provided on a moisture-proof paper having a water vapor barrier layer of Patent Document 7, sufficient gas barrier properties and water vapor barrier properties cannot be achieved at the same time. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 5873770 [Patent Document 2] Patent No. 5671816 [Patent Document 3] Patent No. 6505699 [Patent Document 4] JP 2009-184138 A [Patent Document 5] JP 2003-094574 A [Patent Document 6] Patent No. 5331265 [Patent Document 7] JP 2005-162213 A Summary of the Invention [Problem to be solved by the invention]
[0004] The object of the present invention is to provide a laminate which generates little odor, has excellent barrier properties against oxygen gas and water vapor, absorbs oxygen in a content storage section of the package to reduce the oxygen concentration, and inhibits deterioration of the contents due to oxygen and moisture, and has an excellent balance of low odor properties, low oxygen concentration, low humidity, aroma retention, filling packaging properties, and blocking resistance, and to provide a packaging material and a package produced using the laminate. [Means for solving the problem]
[0005] In order to solve the above problems, the present inventors have found that a laminate including at least a substrate layer, an oxygen barrier layer, and an oxygen absorbing coating layer can solve the above problems. That is, the present invention is characterized in the following points. 1. An oxygen-absorbing coating laminate comprising at least a substrate layer, an oxygen barrier layer, and an oxygen-absorbing coating layer, the oxygen barrier layer includes one or more selected from the group consisting of a metal foil, a resin film with an inorganic vapor deposition layer, a resin coat film or resin film made of an oxygen barrier resin, and a barrier paper; the barrier paper has a layer structure including at least a base paper, a water vapor barrier resin layer, and an oxygen barrier resin layer, in this order, and is laminated so that the oxygen barrier resin layer is located on the oxygen-absorbing coating layer side; The oxygen-absorbing coating layer is a layer formed from an oxygen-absorbing coating composition, The oxygen-absorbing coating composition contains at least an oxygen-absorbing compound and an oxidation-promoting catalyst, The oxygen absorbing compound has one or more unsaturated five-membered rings, any bond between the five carbon atoms constituting the unsaturated five-membered ring is a carbon-carbon double bond; A monovalent and / or divalent or higher electron-donating organic group 1 is bonded to the unsaturated five-membered ring; When the number of the unsaturated five-membered ring is one, the five-membered ring or the organic group 1 has a functional group having an active hydrogen or a group in which the active hydrogen of the functional group having an active hydrogen is substituted with a monovalent organic group 2, When the number of the unsaturated five-membered rings is two or more, the unsaturated five-membered rings are bonded to each other via a divalent or higher organic group 2 which substitutes an active hydrogen of an active hydrogen group on each of the five-membered rings or the organic group 1. Oxygen absorbing coated laminate. 2. The structure of the unsaturated five-membered ring, or the structure consisting of the unsaturated five-membered ring and organic group 1, is derived from one or more members selected from the group consisting of cyclopentadiene, dicyclopentadiene, norbornene, and derivatives thereof. 2. The oxygen-absorbing coated laminate according to 1 above. 3. The organic group 2 includes a structural portion derived from an isocyanate compound, or an isocyanate compound and a hydroxyl group-containing compound. 3. The oxygen-absorbing coated laminate according to 1 or 2 above. 4. The isocyanate compound is xylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, toluene diisocyanate, diphenyl methacrylate, one or more selected from the group consisting of diisocyanate, diisocyanate derivatives thereof, 4. The oxygen-absorbing coated laminate according to 3 above. 5. The hydroxyl group-containing compound is one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof. 5. The oxygen-absorbing coated laminate according to 3 or 4 above. 6. The organic group 2 does not have a crosslinkable functional group. 6. An oxygen-absorbing coated laminate according to any one of 1 to 5 above. 7. The organic group 2 has one or more crosslinkable functional groups, the crosslinkable functional group is a hydroxyl group and / or an isocyanate group; 6. An oxygen-absorbing coated laminate according to any one of 1 to 5 above. 8. The oxygen-absorbing compound contains one or more compounds selected from the group consisting of compounds represented by the following formulas (1) to (4): 6. An oxygen-absorbing coated laminate according to any one of 1 to 5 above. [ka] [ka] [ka] [ka] (In the formula, a to e are each a number of 1 or more, and R 1 , R 2 , R 3 Each of the above is an organic group having one or more carbon atoms and contains at least an alkylene and / or phenylene structure, and further includes polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenylene polyols, and the like. (The polyol may include a structure derived from one or more selected from the group consisting of urethane chain-extended polyols, urethane oxy resins, and urethane chain-extended polyols thereof.) 9. The oxygen-absorbing compound contains a compound represented by the following formula (5): 6. An oxygen-absorbing coated laminate according to any one of 1 to 5 above. [ka] (In the formula, f is a number equal to or greater than 0, and R 4 and R 5Each of the above is an organic group having one or more carbon atoms, containing at least an alkylene and / or phenylene structure, and further may contain a structure derived from one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof. 10. The oxidation-promoting catalyst is a peroxide or a compound containing a cation consisting of a transition metal; 10. An oxygen-absorbing coated laminate according to any one of 1 to 9 above. 11. The compound containing a cation made of a transition metal is a metal soap made of a transition metal compound capable of releasing a cation or complex made of a transition metal and an anion or ligand made of a fatty acid. 11. The oxygen-absorbing coated laminate according to any one of 1 to 10 above. 12. The oxygen-absorbing coating composition further contains a modifying agent, 12. The oxygen-absorbing coated laminate according to any one of the above 1 to 11, wherein the modifying agent contains an isocyanate compound and / or a hydroxyl group-containing compound. 13. The isocyanate compound is one or more selected from the group consisting of xylylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, and derivatives thereof. 13. The oxygen-absorbing coated laminate according to claim 12. 14. The hydroxyl group-containing compound includes one or more selected from the group consisting of polyester polyols, poly(meth)acrylic acid ester polyols, polyalkylene ether diols, and urethane chain-extended polyols thereof, vinyl chloride-vinyl acetate copolymers, cellulose acetate resins, styrene-maleic acid ester copolymers, polyamide resins, and polyimide resins. 14. The oxygen-absorbing coated laminate according to 12 or 13 above. 15. An oxygen-absorbing coated packaging material produced using the oxygen-absorbing coated laminate according to any one of 1 to 14 above. 16. An oxygen-absorbing coated package produced using the oxygen-absorbing coated packaging material according to 15 above, The oxygen barrier layer is a layer located outside the oxygen absorbing coating layer. Oxygen absorbing coated packaging. Effect of the Invention
[0006] According to the present invention, it is possible to obtain a laminate which generates little odor, has excellent barrier properties against oxygen gas and water vapor, absorbs oxygen in the enclosed space to reduce the oxygen concentration, and inhibits deterioration of the contents due to oxygen and moisture, and has an excellent balance of low odor properties, low oxygen concentration, low humidity, aroma retention, filling packaging properties, and blocking resistance, as well as a packaging material and a package produced using said laminate. Furthermore, packaging materials made from the laminate of the present invention are particularly suitable for flexible packaging applications, shortening the packaging process, reducing costs, and making the package lighter. Since the package does not require the inclusion of an oxygen absorber as was previously included, this eliminates the risk of the oxygen absorber being accidentally ingested and reduces the amount of waste consisting of the oxygen absorber. [Brief description of the drawings]
[0007] [Figure 1] 1 is a cross-sectional view showing an example of the oxygen-absorbing coated laminate of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing one example of another embodiment of the oxygen-absorbing coated laminate of the present invention. [Diagram 3] FIG. 2 is a cross-sectional view showing another example of the oxygen-absorbing coated laminate of the present invention. [Figure 4] FIG. 1 is a perspective view showing an example of the oxygen-absorbing coated packaging material of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The present invention will be described in more detail below. The following description of the constituent elements is an example of an embodiment of the present invention, and the present invention is not limited to these contents as long as it does not exceed the gist of the present invention. In the present invention, the terms film and sheet have the same meaning.
[0009] <Oxygen-absorbing coated laminate> The oxygen-absorbing coated laminate of the present invention is a laminate used for packaging materials, and includes a layer structure in which at least a substrate layer, an oxygen barrier layer, and an oxygen-absorbing coated layer are laminated in this order. When an oxygen-absorbing coated packaging material (hereinafter sometimes abbreviated as oxygen-absorbing coated packaging material or packaging material) made from an oxygen-absorbing coated laminate (hereinafter sometimes abbreviated as coated laminate or laminate) is formed into an oxygen-absorbing coated packaging body (hereinafter sometimes abbreviated as packaging body), the oxygen barrier layer is located outside the packaging body relative to the oxygen-absorbing coating layer. By positioning the oxygen barrier layer outside the oxygen-absorbing coating layer, the amount of oxygen passing through the oxygen-absorbing coated packaging from the outside can be reduced, and the efficiency with which the oxygen-absorbing coating layer absorbs oxygen in the content storage space and reduces the oxygen concentration can be increased.
[0010] The oxygen-absorbing coating laminate may contain layers having various other functions, if necessary. For example, it may have a sealant layer or a printed layer, and may include a reinforcing layer to satisfy various conditions such as deformation resistance, drop impact resistance, pinhole resistance, heat resistance, sealability, quality maintenance, workability, hygiene, and the like. In addition, the packaging material may have a functional layer for improving the oxygen gas barrier property, imparting barrier properties against water vapor and the like, imparting aroma retention to the contents to be filled and packaged, and preventing the contents from having an unpleasant taste or odor. Furthermore, an adhesive resin layer may be included between or within each of the above layers in order to improve interlayer adhesion.
[0011] [Contents] In the above, examples of the contents include meat, fresh fish, prepared foods, Japanese sweets, Western sweets, cheese, and the like.
[0012] <Layers Constituting the Oxygen-Absorbing Coating Laminate> <Oxygen barrier layer> The oxygen barrier layer is a layer that inhibits oxygen from passing from the outside of the package to the content-accommodating section inside the package when the package is produced using a packaging material made of the oxygen-absorbing coated laminate. When the package is produced, the oxygen barrier layer is located outside the oxygen absorbing coating layer. This makes it possible to suppress the penetration of oxygen from the outside of the package, and to enhance the effect of the oxygen-absorbing coating layer absorbing oxygen in the content storage space of the package and reducing the oxygen concentration. The oxygen barrier layer can be made of various oxygen barrier materials. In addition, the oxygen barrier layer may be made of an oxygen barrier material that has gas barrier properties not only against oxygen but also against water vapor, light blocking properties against sunlight, aroma retention properties for the contents, etc. In addition, a barrier material that has gas barrier properties against water vapor, light blocking properties against sunlight, aroma retention properties for the contents, etc. may be used in combination.
[0013] Specifically, the oxygen barrier material may be one or more selected from the group consisting of metal foil, a resin film with an inorganic vapor deposition layer, a resin coat film or film made of an oxygen barrier resin, and barrier paper. Examples of the inorganic compound in the inorganic vapor deposition layer include metals, metal oxides, metal nitrides, and metal carbides. Among the above, resin films with a metal vapor deposition layer, resin films with a metal oxide vapor deposition layer, and resin coated films or resin films made of a barrier resin are particularly preferred, as they have excellent barrier properties against oxygen gas, water vapor, light blocking, aroma retention, etc., and are environmentally friendly in terms of disposal of the container.
[0014] [Metal foil] A specific example of the metal foil is aluminum foil, which has a thickness of preferably 4 μm to 40 μm, more preferably 4 μm or more and 12 μm or less, and even more preferably 5 μm or more and 9 μm or less.
[0015] [Resin film with inorganic vapor deposition layer] Specific examples of inorganic compounds constituting the inorganic vapor deposition layer include metals, metal oxides, metal nitrides, and metal carbides. Specific examples of metal elements constituting the above inorganic compounds include aluminum (Al), silicon (Si), magnesium (Mg), calcium (Ca), potassium (K), tin (Sn), sodium (Na), boron (B), titanium (Ti), lead (Pb), zirconium (Zr), yttrium (Y), zinc (Zn), vanadium (V), barium (Ba), and chromium (Cr).
[0016] Specific examples of inorganic compounds include metals, metal oxides, metal nitrides, and metal carbides made of the above-mentioned metal elements. In addition, indium tin oxide (ITO), SiO x C y Also included are composite inorganic compounds such as membranes. More specific examples of the inorganic compound include silicon oxide, aluminum oxide, silicon nitride, silicon carbide, etc. Among these, silicon oxide and aluminum oxide are preferred.
[0017] The average composition of an inorganic compound is expressed as, for example, SiO x , AlO x , SiO x C y MO x , M.O. x C y(wherein, M represents a metal element, and the ranges of the values of x and y vary depending on the metal element.) In the case of metal oxides, the range of the value of x can be in the following ranges: silicon: 0-2, aluminum: 0-1.5, magnesium: 0-1, calcium: 0-1, potassium: 0-0.5, tin: 0-2, sodium: 0-0.5, boron: 0-1.5, titanium: 0-2, lead: 0-1, zirconium: 0-2, and y: 0-1.5. In the above MOX, when x=0, it is metallic and not transparent, and the upper limit of the range of x is the value when it is completely oxidized. Silicon oxide having an x value in the range of 1.0 to 2.0, and aluminum oxide having an x value in the range of 0.5 to 1.5 can be used. The oxygen barrier layer may be formed of one of these barrier materials, or may be formed by combining two or more of them, or may be formed by mixing two or more of them. The laminate may be made up of multiple layers having the same or different compositions, and in the case of multiple layers, they do not have to be laminated adjacently.
[0018] The resin film supporting the inorganic vapor deposition layer may be the same as the resin film constituting the base layer. However, since the inorganic vapor deposition layer is formed on a resin film, it is preferable to use a resin film that has excellent mechanical, physical, chemical and other properties, and is particularly strong and tough, and has heat resistance.
[0019] Specifically, in the present invention, examples of the resin film supporting the inorganic vapor deposition layer include polyester-based resin films such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT), polyamide-based resin films such as various nylons, polyethylene-based resins, polypropylene-based resins, cyclic polyolefin resins, polystyrene-based resins, acrylonitrile-styrene copolymers (AS resins), acrylonitrile-butadiene-styrene copolymers (ABS resins), polyolefin films such as polybutene resin films, polyvinyl chloride-based resins, polycarbonate-based resins, polyimide-based resins, polyamideimide-based resins, polyarylphthalate resins, silicone-based resins, polysulfone-based resins, polyphenylene sulfide-based resins, polyethersulfone-based resins, polyurethane-based resins, cellulose-based resins, poly(meth)acrylic resins, polyvinylidene chloride films, acetal-based resin films, fluorine-based resins, and others. In the present invention, it is preferable to use a resin film made of biaxially oriented polyethylene terephthalate, polyacrylonitrile, ethylene-vinyl alcohol copolymer, non-oriented polypropylene (CPP), low-density polyethylene, linear low-density polyethylene, or the like, which can be heat-sealed or bonded with an adhesive.
[0020] As a method for forming an inorganic vapor deposition layer, the inorganic vapor deposition layer can be formed on a resin film using, for example, a physical vapor deposition method (Physical Vapor Deposition method, PVD method) such as a vacuum deposition method, a sputtering method, an ion plating method, a cluster ion beam method, or a chemical vapor deposition method (Chemical Vapor Deposition method, CVD method) such as a plasma chemical vapor deposition method, a thermal chemical vapor deposition method, a photochemical vapor deposition method, or the like, using the inorganic compounds as raw materials.
[0021] More specifically, in the above-mentioned PVD method, for example, a take-up type deposition machine is used, and a resin film coming off a winding roll in a vacuum chamber is placed into a deposition chamber, where a deposition source heated in a crucible is evaporated, and if necessary, an inorganic deposition layer is formed on the resin film on a cooled coating drum through a mask while oxygen or the like is sprayed from an oxygen outlet, and then the resin film with the inorganic deposition layer formed thereon is wound up onto a take-up roll, thereby producing a resin film with an inorganic deposition layer according to the present invention.
[0022] Meanwhile, in the above-mentioned CVD method, a mixed gas of, for example, an organic silicon compound as a monomer gas, oxygen gas, an inert gas, etc., supplied from a vapor deposition raw material volatilization and supply device in the vapor deposition chamber, is introduced onto the surface of a resin film unwound from a winding roll arranged in a vapor deposition chamber, on the peripheral surface of a cooling electrode drum, and a resin film on which a vapor deposition layer of silicon oxide is formed by plasma can be produced.
[0023] In the above, the thickness of the inorganic vapor deposition layer is preferably 30 Å to 3000 Å, more preferably 40 Å to 2500 Å, and even more preferably 50 Å to 2000 Å, in order to obtain sufficient oxygen barrier properties. More specifically, in the above PVD method, the thickness of the inorganic vapor deposition layer made of aluminum oxide is preferably 30 Å to 1000 Å, and more preferably about 50 Å to 500 Å. In the above CVD method, the thickness of the inorganic vapor deposition layer made of silicon oxide is preferably 30 Å to 3000 Å, and more preferably 100 Å to 300 Å. In the above, in the case of an inorganic vapor deposition layer made of a metal oxide or an inorganic substance, if the thickness of the inorganic vapor deposition layer exceeds the above range, cracks or the like are likely to occur in the inorganic vapor deposition layer, which may result in a decrease in barrier properties and may also lead to problems such as an increase in material costs, which is undesirable. Also, if the thickness is less than the above range, it is undesirable because it may be difficult to achieve oxygen barrier properties.
[0024] The resin film with an inorganic deposition layer preferably has a water vapor permeability of 3.0 g / m2 or less, as measured in accordance with JIS K7129 at a temperature of 40° C. and a humidity of 100% RH. 2 ·day or less, and more preferably 2.0 g / m 2 ·day or less, and more preferably 1.5 g / m 2 If the water vapor transmission rate is within the above range, the intrusion of water vapor from the outside of the package into the content-accommodating portion inside the package can be sufficiently suppressed. The resin film with an inorganic vapor deposition layer preferably has an acid permeability of 3.0 cc / m2 or less as measured in accordance with JIS K7126 under an environment of 23°C temperature and 90% RH. 2 ·atm·day or less, and more preferably 1.0cc / m 2 ·atm·day or less, and more preferably 0.5cc / m 2 If the oxygen permeability falls within the above range, the intrusion of oxygen from the outside of the package into the content-accommodating portion inside the package can be sufficiently suppressed.
[0025] When forming the inorganic deposition layer, SiO x By pretreating the surface of the resin film to be vapor-deposited with plasma or the like, the surface can be cleaned and polar groups, free radicals, etc. can be generated on the surface, thereby increasing the adhesion between the inorganic vapor-deposited layer and the resin film. Furthermore, when two or more inorganic vapor deposition layers are continuously laminated using a plasma enhanced chemical vapor deposition apparatus consisting of at least two deposition chambers, each layer can be deposited so as to have high gas barrier properties, thereby achieving gas barrier properties that are even higher than those of a single layer. Furthermore, by continuously depositing the layers without exposing them to the atmosphere, it is possible to prevent foreign matter, dust, etc., which may cause cracks, from being mixed between the inorganic vapor deposition layers, and the gas barrier properties are improved. Furthermore, if the compositions of the vapor-deposited layers are different, the inorganic vapor-deposited layers are different discontinuous layers, so that the permeation of oxygen gas, water vapor, etc. can be more efficiently suppressed.
[0026] When the oxygen barrier layer is formed of a resin film with an inorganic vapor deposition layer, it can be laminated via an adhesive resin layer. When laminating a resin film with an inorganic vapor deposition layer, if necessary, in order to strengthen the adhesive strength with other layers, the surface of the resin film with an inorganic vapor deposition layer may be subjected in advance to a physical surface treatment such as corona discharge treatment, ozone treatment, plasma treatment, glow discharge treatment, sandblasting treatment, etc., or a chemical surface treatment such as oxidation treatment using chemicals, to form a surface treatment layer.
[0027] [Resin-coated membrane or resin film made of oxygen barrier resin] An oxygen barrier resin coating film or an oxygen barrier resin film made of an oxygen barrier resin can also be used as an oxygen barrier material, and can simultaneously exhibit gas barrier properties against water vapor and the like, aroma retention, and the like. Examples of oxygen barrier resins include polyvinyl chloride resins, polyvinylidene chloride resins (PVDC), polyester resins (particularly modified PET), polyamide resins (particularly aromatic polyamides such as nylon MXD6), ethylene-vinyl acetate copolymers (EVOH) with an ethylene content of 25 mol % to 50 mol % obtained by completely saponifying ethylene-vinyl acetate copolymers (vinyl acetate is approximately 79 wt % to 92 wt %), polyvinyl alcohol resins, poly(meth)acrylic resins, poly(meth)acrylonitrile resins, and polystyrene resins. For example, resins having excellent gas barrier properties, such as polycarbonate resins, etc., can be used. The resin film used in the resin film made of an oxygen barrier resin may be a resin film constituting a base layer. The thickness of the resin coating film made of the oxygen barrier resin is not limited, but is preferably 0.5 μm to 300 μm, and more preferably 1 μm to 100 μm. The thickness of the resin film made of the oxygen barrier resin is not limited, but is preferably 0.5 μm to 300 μm, and more preferably 1 μm to 100 μm.
[0028] The method for forming a resin coating film made of an oxygen barrier resin is not particularly limited, and the resin coating film can be formed by applying the resin once or multiple times using a conventionally known method such as roll coating, spray coating, spin coating, dipping, brush coating, bar coating, or applicator coating. There is no particular limitation on the method for forming the resin film made of the oxygen barrier resin, and for example, the resin film may be formed by a T-die (co)extrusion method or the like. When laminating a resin coat film or resin film made of an oxygen barrier resin, it can be laminated via an adhesive resin layer, and if necessary, in order to strengthen the adhesive strength with other layers, the surface of the resin coat film or resin film made of an oxygen barrier resin can be previously subjected to a physical surface treatment such as corona discharge treatment, ozone treatment, plasma treatment, glow discharge treatment, sandblasting treatment, etc., or a chemical surface treatment such as oxidation treatment using chemicals, to form a surface treatment layer.
[0029] [Barrier paper] The barrier paper is a paper material with gas barrier properties, and has a layer structure including at least a base paper and an oxygen barrier resin layer, and is laminated so that the oxygen barrier resin layer is located on the oxygen-absorbing coating layer side. The barrier paper preferably further has a protective resin layer on at least one surface, and more preferably has a protective resin layer on the surface on the oxygen barrier resin layer side. The oxygen barrier resin layer of the barrier paper may also serve as a water vapor barrier layer, or the barrier paper may further include a separate water vapor barrier layer between the base paper and the oxygen barrier resin layer. By including each layer in the barrier paper in the above order, the water vapor barrier resin layer prevents moisture contained in the base paper from penetrating into the oxygen barrier resin layer, thereby preventing deterioration of the oxygen barrier resin layer due to said moisture, and therefore preventing deterioration of the oxygen barrier properties of the barrier paper. The protective resin layer is a layer for preventing deterioration of the water vapor barrier resin layer and the gas barrier layer due to moisture in the air and the like, and further, by having a protective resin layer, the oxygen barrier property and water vapor barrier property of the barrier paper are further improved, or it can impart properties such as oil resistance, solvent resistance, heat resistance, abrasion resistance, impact resistance and light resistance. The base paper may be a paper base material that constitutes the base layer. The water vapor permeability of the barrier paper is 10g / m at 40℃ and relative humidity of 90±2%. 2 ·day or less, and the oxygen permeability is 3cc / m at 23℃ and 0% relative humidity. 2 ·day·atm or less is preferable, and 3cc / m at 23°C and 85% relative humidity 2 ·day·atm or less is preferable.
[0030] (Oxygen barrier resin layer) The oxygen barrier resin layer is a layer that suppresses oxygen permeation, and is preferably a coating layer formed from an oxygen barrier resin composition. The oxygen barrier resin composition contains at least a water-soluble polymer, and may further contain a pigment, a crosslinking agent, and a surfactant, if necessary, in order to improve the oxygen barrier property. The content of the pigment in the oxygen barrier resin layer is preferably 1 / 100 to 1000 / 100 in terms of the dry mass ratio of the pigment to the water-soluble polymer. If the dry mass ratio is outside the above range, the oxygen barrier property is deteriorated. There is a risk that the improvement effect will be reduced. The crosslinking agent can crosslink the water-soluble polymer, thereby making the oxygen barrier resin layer dense and improving the oxygen barrier property. Furthermore, the oxygen barrier resin composition may further contain various commonly used auxiliaries, such as dispersants, thickeners, water retention agents, defoamers, water resistance agents, dyes, and fluorescent dyes, as necessary.
[0031] The coating method for forming an oxygen barrier resin layer using the oxygen barrier resin composition is not particularly limited, and coating can be performed using a known coating device and coating system. Examples of coating devices include a blade coater, a bar coater, a roll coater, an air knife coater, a reverse roll coater, a curtain coater, a spray coater, a size press coater, and a gate roll coater. Examples of coating systems include water-based coating using a solvent such as water, and solvent-based coating using a solvent such as an organic solvent. The oxygen barrier resin layer can be dried by any known method, including, for example, a method using a steam heater, a gas heater, an infrared heater, an electric heater, a hot air heater, a microwave, a cylinder dryer, or the like. The coating weight of the oxygen barrier resin layer is 0.2 g / m2 in dry weight. 2 More than 20g / m 2 If the coating amount is less than the above range, the thickness of the oxygen barrier resin layer is likely to be non-uniform, and there is a risk that sufficient oxygen barrier properties will not be obtained, whereas if it is more than the above range, the drying load during coating will be large.
[0032] The oxygen barrier resin layer may be composed of one layer, or may be composed of two or more layers of the same or different compositions. When the oxygen barrier resin layer is composed of two or more layers, it is preferable that the total coating amount of all layers is within the above range. The surface tension of the oxygen barrier resin layer is preferably from 10 mN / m to 60 mN / m, more preferably from 15 mN / m to 50 mN / m. When the surface tension of the oxygen barrier resin layer is in the above range, the adhesion to the water vapor barrier resin layer is improved. Furthermore, the difference between the wetting tension of the surface of the water vapor barrier resin layer and the surface tension of the oxygen barrier resin layer is preferably within ±20 mN / m. By having the difference within the above range, the adhesion between the oxygen barrier resin layer and the water vapor barrier resin layer is improved. When the oxygen barrier resin layer also serves as a water vapor barrier layer, the oxygen barrier resin composition can exhibit water vapor barrier properties by further containing the same components as the water vapor barrier composition described below.
[0033] (Water vapor barrier layer) The water vapor barrier layer is a layer that suppresses the transmission of water vapor, and is preferably a coating layer formed from a water vapor barrier composition. The water vapor barrier composition contains at least a water vapor barrier resin and / or a water vapor barrier inorganic material (hereinafter, both of which are collectively referred to as the water vapor barrier component), and may further contain a pigment and / or a crosslinking agent to improve the water vapor barrier properties, if necessary. In addition, it may contain a water-soluble polymer, provided that the water vapor barrier properties are not adversely affected. The content of the pigment in the water vapor barrier layer is preferably 30% by mass or more and 95% by mass or less, and more preferably 40% by mass or more and 90% by mass or less, in terms of the dry mass of the pigment. The pigment can improve the water vapor barrier properties and improve the adhesion between the water vapor barrier layer and the oxygen barrier resin layer, and the crosslinking agent can improve the water vapor barrier properties by densifying the water vapor barrier layer by crosslinking the water vapor barrier resin and the water-soluble polymer. Furthermore, the water vapor barrier composition may contain various commonly used auxiliary agents, such as water repellents, dispersants, thickeners, water retention agents, defoamers, water resistance agents, dyes, and fluorescent dyes, as necessary.
[0034] The coating method for forming the water vapor barrier layer using the water vapor barrier composition is not particularly limited, and coating can be performed using a known coating device and coating system. For example, Examples of the coating machine include a blade coater, a bar coater, a roll coater, an air knife coater, a reverse roll coater, a curtain coater, a spray coater, a size press coater, a gate roll coater, etc. Examples of the coating system include water-based coating using a solvent such as water, and solvent-based coating using a solvent such as an organic solvent.
[0043] As a method for drying the water vapor barrier layer, a known method can be used, and examples thereof include a method using a steam heater, a gas heater, an infrared heater, an electric heater, a hot air heater, a microwave, a cylinder dryer, etc. The coating amount of the water vapor barrier composition is 3 g / m2 on a dry basis. 2 More than 50g / m 2 Less than 5 g / m is preferable. 2 More than 40g / m 2 Less than 7 g / m is more preferable. 2 More than 30g / m 2 If the coating amount is smaller than the above range, the thickness of the water vapor barrier layer is likely to be non-uniform, and there is a risk that sufficient water vapor barrier properties will not be obtained, whereas if it is larger than the above range, the drying load during coating will be large.
[0035] In the present invention, the water vapor barrier layer may be composed of one layer, or may be composed of two or more layers of the same or different compositions. When the water vapor barrier layer is composed of two or more layers, it is preferable that the total coating amount of all layers is within the above range. The wetting tension of the water vapor barrier layer surface is preferably 10 mN / m or more and 60 mN / m or less, and more preferably 15 mN / m or more and 50 mN / m or less. When the wetting tension of the water vapor barrier layer surface is in the above range, the water vapor barrier property is improved, and the adhesion with the oxygen barrier resin layer is improved.
[0036] (Protective resin layer) The protective resin layer is a layer containing a resin and may be composed of one layer or two or more layers of the same or different compositions, and may further include a layer made of a metal foil or a layer made of an inorganic vapor deposition film. Resins that may be contained in the protective resin layer include polyester, polyvinyl alcohol, polypropylene, polyethylene, polystyrene, polyethylene terephthalate, polybutylene terephthalate, polymethylpentene, polyvinyl chloride, acrylonitrile-butadiene-styrene, acrylonitrile-styrene, poly(meth)acrylic, polyvinylidene chloride, polyamide (nylon), polyacetal, polycarbonate, polylactic acid (PLA), esterified starch, cellulose acetate, polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), and the like. The protective resin layer may be an extrusion layer formed by melt (co)extrusion, or may be an attachment layer formed by bonding a resin film by a dry lamination method, a sand lamination method, or the like. As the resin film, among the above-mentioned resins, those containing polyvinyl alcohol, ethylene-vinyl alcohol copolymer, polyvinylidene chloride, polyacrylonitrile, or the like as the main component, or resin films formed by coating these resins on resin films made of the above-mentioned resins are preferred. Alternatively, a resin film with a metal foil can be used in which a metal foil made of various metals such as aluminum is laminated to a resin film made of the above-mentioned resin, or a resin film with an inorganic vapor deposition layer can be used in which various metals such as aluminum and / or inorganic oxides such as silicon oxide and aluminum oxide are vapor-deposited onto a resin film made of the above-mentioned resin.
[0037] (Water vapor barrier resin) The water vapor barrier resin is preferably a (co)polymer synthesized from one or more monomers selected from the group consisting of styrene, alkene, (meth)acrylic monomers, vinyl acetate monomers, and maleic acid monomers. Specific examples of water vapor barrier resins include styrene-butadiene copolymer resins, styrene-acrylic copolymer resins, ethylene-vinyl acetate copolymer resins, and various paraffin ( WAX-based compounds, butadiene-methyl methacrylate copolymer-based resins, vinyl acetate-butyl acrylate copolymer-based resins, acrylic acid-methyl methacrylate copolymer-based resins, copolymer-based resins in which maleic anhydride is added to the above-mentioned resin raw materials, etc. Among these, styrene-butadiene copolymer-based resins are preferred due to their high water vapor barrier properties. The water vapor barrier resin may be further modified by combining various comonomers and emulsion-polymerizing them. Examples of the comonomer include methyl methacrylate, acrylonitrile, acrylamide, hydroxyethyl acrylate, and unsaturated carboxylic acids such as itaconic acid, maleic acid, and acrylic acid. As the emulsifier, anionic surfactants such as sodium oleate, rosin acid soap, sodium alkylarylsulfonate, and sodium dialkylsulfosuccinate may be used alone or in combination with a nonionic surfactant. Depending on the purpose, an amphoteric or cationic surfactant may be used.
[0038] (Inorganic water vapor barrier) As the water vapor barrier inorganic material, it is preferable to use one or more types selected from the group consisting of kaolin, clay, engineered kaolin, delaminated clay, heavy calcium carbonate, light calcium carbonate, mica, talc, titanium dioxide, barium sulfate, calcium sulfate, zinc oxide, silicic acid, silicates, colloidal silica, and satin white.
[0039] (Water-soluble polymer) The water-soluble polymer contained in the oxygen barrier resin composition and / or the water vapor barrier resin composition is preferably a polyvinyl alcohol resin, polyvinylpyrrolidone, polysaccharides, proteins, etc. Specific examples of polyvinyl alcohol resins include fully saponified polyvinyl alcohol, partially saponified polyvinyl alcohol, and ethylene copolymerized polyvinyl alcohol. Examples of the polysaccharides include cellulose resins and starches. Specific examples of the cellulose resins include carboxymethyl cellulose, hydroxymethyl cellulose, and hydroxyethyl cellulose. Specific examples of the starches include oxidized starch, cationized starch, urea phosphate esterified starch, and hydroxyethyl etherified starch. Among these, polyvinyl alcohol-based resins and cellulose-based resins are preferred, and polyvinyl alcohol-based resins are more preferred.
[0040] (Pigments) The shape of the pigment particles contained in the water vapor barrier resin composition and / or the oxygen barrier resin composition is preferably flat, and the average aspect ratio is preferably at least 10. Furthermore, the pigment particles preferably have a volume-based 50% particle size (D50, hereinafter referred to as the average particle size) of 5 μm or more. In a layer containing a pigment, water vapor and oxygen attempt to pass through by bypassing the pigment, but if the pigment particles are flat, have a high aspect ratio, or have a high pigment content, the number of bypasses and the distance traveled are increased, thereby improving the water vapor barrier property and / or oxygen barrier property.
[0041] Furthermore, it is more preferable to use a pigment having an average particle size of 5 μm or less in combination. By using a pigment with an average particle size of 5 μm or more in combination with a pigment with an average particle size of 5 μm or less, the pigment distribution in the water vapor barrier resin layer and / or the oxygen barrier resin layer can be brought closer to close-packed, thereby increasing the volume percentage of the pigment and improving the water vapor barrier property and / or the oxygen barrier property. In this case, the dry weight ratio of the pigment having an average particle size of 5 μm or more to the pigment having an average particle size of 5 μm or less is preferably 50 / 50 to 99 / 1. If the amount of pigments with an average particle size of 5 μm or less is less than the above range, the combined effect is not fully exerted. If the amount is more than the above range, the number of detours and the distance traveled by oxygen and water vapor are reduced, and the combined effect is likely to deteriorate. When the pigment is mixed into the water-soluble polymer, it is preferable to mix the pigment in a slurry form.
[0042] As the pigment, inorganic pigments such as kaolin, clay, engineered kaolin, delaminated clay, heavy calcium carbonate, light calcium carbonate, mica, talc, titanium dioxide, barium sulfate, calcium sulfate, zinc oxide, silicic acid, silicate salts, colloidal silica, satin white, etc., and organic pigments such as solid type, hollow type, and core-shell type can be used alone or in combination of two or more types. Among the above, inorganic pigments are preferred. As the flat pigment, inorganic pigments such as kaolin, mica, and talc are preferred, and kaolin is more preferred. Examples of pigments having an average particle size of 5 μm or less that can be used in combination with pigments having an average particle size of 5 μm or more and an aspect ratio of 10 or more include inorganic pigments such as kaolin, clay, engineered kaolin, delaminated clay, heavy calcium carbonate, light calcium carbonate, talc, titanium dioxide, barium sulfate, calcium sulfate, zinc oxide, silicic acid, silicates, colloidal silica, and satin white, as well as organic pigments such as solid, hollow, and core-shell types. Among these pigments, heavy calcium carbonate is preferred.
[0043] (Crosslinking agent)
[0081] There are no particular limitations on the type of crosslinking agent contained in the water vapor barrier resin composition and / or the oxygen barrier resin composition, and polyvalent metal salts, amine compounds, amide compounds, aldehyde compounds, hydroxy acids, etc. may be appropriately selected and used in accordance with the type of water vapor barrier resin or water-soluble polymer. Here, the polyvalent metal salt is formed from a polyvalent metal ion and various ionic substances, such as copper, zinc, silver, iron, potassium, sodium, zirconium, aluminum, calcium, barium, magnesium, titanium, etc., and the various ionic substances include carbonate ions, sulfate ions, nitrate ions, phosphate ions, silicate ions, nitrogen oxides, boron oxides, etc. Among the above, polyvalent metal salts are preferred, and potassium aluminum sulfate (potassium alum) is more preferred. In particular, when the resin composition contains a copolymer containing styrene, polyvalent metal salts are preferred, and potassium aluminum sulfate (potassium alum) is more preferred.
[0044] The content of the crosslinking agent is not particularly limited as long as it is within the range of the paint concentration and viscosity that can be applied, but the amount of the crosslinking agent is preferably 1 part by mass or more and 10 parts by mass or less, and more preferably 3 parts by mass or more and 5 parts by mass or less, relative to 100 parts by mass of the total amount of the water vapor barrier resin and the water-soluble polymer. If the amount of crosslinking agent is less than the above range, there is a risk that the effect of adding the crosslinking agent will not be fully obtained, and if the amount is more than the above range, the viscosity will increase significantly, making coating difficult. When adding a crosslinking agent, it is preferable to add it after dissolving it in a polar solvent. When a crosslinking agent is dissolved in a polar solvent, a bond is formed between the crosslinking agent and the polar solvent, so even if the crosslinking agent is added, a crosslinking reaction with the water vapor barrier resin or the water-soluble polymer does not immediately occur until the polar solvent evaporates, and therefore thickening of the paint can be suppressed.
[0045] (Water repellent) The water repellent agent can improve the water vapor barrier property by its water repellent effect. Specific examples of water repellents include paraffin-based water repellents mainly made of alkane compounds, natural oil-based water repellents derived from plants and animals such as carnauba and lanolin, silicone-containing water repellents containing silicone or silicone compounds, and fluorine-containing water repellents containing fluorine compounds. These water repellents can be used alone or in combination of two or more kinds. Among these, paraffin-based water repellents are preferred. The content of the water repellent is not particularly limited, but it is preferably from 1 part by mass to 100 parts by mass per 100 parts by mass of the total of the water vapor barrier resin and the water-soluble polymer. If the content of the water repellent is less than the above range, there is a risk that the effect of improving the water vapor barrier property will not be sufficiently obtained, and if it is more than the above range, there is a risk that it will be difficult to form another layer uniformly when forming it on the water vapor barrier resin layer containing the water repellent.
[0046] (Surfactant) The surfactant improves the leveling property of the oxygen barrier resin composition and / or the water vapor barrier resin composition, improves the uniformity of the layer to be formed, and improves the interlayer adhesion, thereby improving the water vapor barrier property and oxygen barrier property. There is no limitation on the ionicity of the surfactant, and any of anionic surfactants, cationic surfactants, amphoteric surfactants, and nonionic surfactants can be used alone or in combination of two or more kinds. Specific examples of the surfactant include silicone surfactants, fluorine surfactants, alcohol surfactants, acetylene surfactants having an acetylene group, acetylene diol surfactants having an acetylene group and two hydroxyl groups, alkylsulfonic acid surfactants having an alkyl group and sulfonic acid, ester surfactants, amide surfactants, amine surfactants, alkyl ether surfactants, phenyl ether surfactants, sulfate ester surfactants, phenol surfactants, etc. Among these, acetylene diol surfactants are preferred.
[0047] <Oxygen-absorbing coating layer> The oxygen-absorbing coating layer is a layer formed using an oxygen-absorbing coating agent composition.
[0048] <Oxygen-absorbing coating composition> The oxygen-absorbing coating composition contains at least an oxygen-absorbing compound and an oxidation-promoting catalyst. The oxygen-absorbing coating composition may further contain a modifier, a diluting solvent, various additives, and the like, as required. The oxygen-absorbing coating composition can also be used as a printing ink binder.
[0049] The oxygen-absorbing coating composition may be prepared by adding the oxygen-absorbing compound to an existing coating composition, or the oxygen-absorbing coating composition may be prepared using the oxygen-absorbing compound as a resin component. Here, the existing coating composition may be a one-liquid coating composition or a two-liquid coating composition. The oxygen-absorbing coating composition can contain one or more oxygen-absorbing compounds. The oxygen-absorbing coating composition and / or the above-mentioned existing coating composition may be curable or non-curable. If it is curable, it may be any of heat curable, photocurable, electron beam curable, etc. The oxygen absorbing compound may or may not react with components contained in existing coating compositions, or may react with other oxygen absorbing compounds. Depending on the presence or absence of the above reaction and the type of reaction, one or more oxygen absorbing compounds can be selected and used from among those having no functional group, those having a (co)polymerizable functional group, and those having a functional group capable of reacting as a base agent or a curing agent.
[0050] Specifically, for example, a two-liquid urethane coating composition containing an isocyanate compound and a hydroxyl group-containing compound is mixed with an oxygen absorbing compound having no functional group and / or a functional compound. In this case, the functional group is preferably an isocyanate group and / or a hydroxyl group. In addition, for example, the oxygen-absorbing coating composition can be prepared by combining the main component and curing agent with an isocyanate compound and an oxygen-absorbing compound having a hydroxyl group, with a hydroxyl group-containing compound and an oxygen-absorbing compound having an isocyanate group, or with an oxygen-absorbing compound having a hydroxyl group and an oxygen-absorbing compound having an isocyanate group. The oxygen-absorbing coating composition is preferably a urethane-based oxygen-absorbing coating composition.
[0051] The solid content in the oxygen-absorbing coating agent composition is not particularly limited, but is preferably 20% by mass or more and 100% by mass or less.
[0052] The content of the oxygen absorbing compound in the solid content excluding the oxidation-promoting catalyst in the oxygen absorbing coating composition is preferably 30% by mass or more and 100% by mass or less. If it is less than the above range, there is a risk that the oxygen absorption property will be insufficient. When it is 100% by mass, it means that the oxygen absorbing compound can be used as a resin component of the coating composition, and it has sufficient coating properties by itself, has a functional group that can be cured by itself, or is used by mixing an oxygen absorbing compound having a functional group as a main agent and an oxygen absorbing compound having a functional group as a curing agent.
[0053] The content of the oxidation-promoting catalyst in the oxygen-absorbing coating composition is preferably 10 ppm or more and 6000 ppm or less based on the total solid content. If the content is less than the above range, the oxygen absorption may be insufficient, and if the content is more than the above range, the oxygen absorption is likely to become unstable, and the oxygen absorption may be consumed before the package is produced, which may impair the effect of inhibiting deterioration of the package contents due to oxygen after the package is produced.
[0054] [Oxygen absorbing compound] The oxygen absorbing compound of the present invention has oxygen absorbing properties, generates little odor, and can be used alone or as a mixture with a resin or a resin composition. The oxygen-absorbing compound of the present invention is an unsaturated five-membered ring-containing compound having one or more unsaturated five-membered rings, in which any bond between five carbon atoms constituting the unsaturated five-membered ring is a carbon-carbon double bond, and a monovalent and / or divalent or higher electron-donating organic group 1 is bonded to the unsaturated five-membered ring. When there is one unsaturated five-membered ring, the five-membered ring or the organic group 1 has a functional group having active hydrogen, or a group in which the active hydrogen of the functional group having active hydrogen is substituted with a monovalent organic group 2, and when there are two or more unsaturated five-membered rings, the unsaturated five-membered rings are bonded to each other via a divalent or higher organic group 2 that substitutes the active hydrogen of the active hydrogen group on each of the organic groups 1. When there are two or more such unsaturated five-membered rings in one molecule, the unsaturated five-membered rings are bonded to each other via a structure in which an active hydrogen of a functional group having an active hydrogen on each of the five-membered rings or organic group 1 is substituted with a divalent or higher organic group 2. The unsaturated five-membered ring, organic group 1, and organic group 2 present in one molecule may each be one or two or more kinds, and the number may be one or two or more. The organic group 1 bonded to one unsaturated five-membered ring may be one or two or more. Furthermore, the oxygen-absorbing compound may be a mixture of molecules having two or more structures in which the types and numbers of the unsaturated five-membered ring, organic group 1, and organic group 2 present in one molecule are different, as described above.
[0055] Organic group 1 donates electrons to the unsaturated five-membered ring, thereby increasing the electron density of the carbon-carbon double bond portion of the unsaturated five-membered ring, thereby increasing the reactivity with oxygen and improving the oxygen absorbency. It is preferable that no electron-withdrawing group is bonded to the unsaturated five-membered ring, since the electron-withdrawing group is bonded to the unsaturated five-membered ring, the electron density of the carbon-carbon double bond portion of the unsaturated five-membered ring is lowered, the reactivity with oxygen is reduced, and the oxygen absorption is reduced. Specific molecular structures of the oxygen-absorbing compound include, for example, one unsaturated five-membered ring bonded to a monovalent or divalent organic group 1, one unsaturated five-membered ring bonded to a monovalent or divalent organic group 1 and a monovalent organic group 2 in that order, two unsaturated five-membered rings bonded via a divalent organic group 1 and a divalent organic group 2, and three unsaturated five-membered rings bonded via a divalent organic group 1 and a trivalent organic group 2.
[0056] In addition, the oxygen absorbing compound does not have to have a crosslinkable functional group, but can have one. The crosslinkable functional group may be a functional group that was possessed by the compound from which the organic group 2 is derived, or may be a functional group that has been added by chemical modification. Because the oxygen-absorbing compound has a crosslinkable functional group, when the oxygen-absorbing compound is mixed with a resin or a resin composition, the oxygen-absorbing compound has increased compatibility with the resin or the resin composition or becomes part of the crosslinked structure of the resin or the resin composition, making it less likely to bleed from the resin or the resin composition, or from the cured product of the resin composition, and the content of the oxygen-absorbing compound in the resin or the resin composition can be increased. Specific examples of the crosslinkable functional group include an aliphatic hydroxyl group, an aromatic hydroxyl group, an isocyanate group, an amino group, an epoxy group, a (meth)acrylic group, etc. Among these, an isocyanate group and an aliphatic hydroxyl group are preferred. When the oxygen-absorbing compound has a crosslinkable functional group, the number of the crosslinkable functional group in one molecule is preferably 1 or 2 or more. In addition, the crosslinkable functional group contained in one molecule may be one type or two or more types. The functional group equivalent of the crosslinkable functional group is not particularly limited, but is preferably 500 to 20,000, more preferably 1,000 to 15,000, and even more preferably 1,500 to 10,000.
[0057] The number average molecular weight of the oxygen absorbing compound is preferably 100 to 10,000, more preferably 200 to 5,000, and even more preferably 300 to 2,500. If the number average molecular weight is smaller than the above range, it is likely to precipitate when mixed with a resin or a resin composition. If the number average molecular weight is larger than the above range, it is likely to require a large amount of dilution solvent to be contained when mixed with a resin or a resin composition because the viscosity of the mixture increases, making it difficult to obtain a thick film or layer, and coating suitability is likely to deteriorate.
[0058] The oxygen absorbing action of the oxygen absorbing compound of the present invention can be promoted by heating or adding a catalyst.
[0059] (unsaturated five-membered ring) The unsaturated five-membered ring of the oxygen-absorbing compound has a carbon-carbon double bond therein. Here, the carbon-carbon double bond is any bond between the five carbon atoms constituting the unsaturated five-membered ring, and there may be one or two carbon-carbon double bonds in one unsaturated five-membered ring. The carbon-carbon double bond reacts with oxygen molecules in the air and captures the oxygen molecules, thereby causing the oxygen absorbing compound to exhibit its oxygen absorbing properties. Examples of compounds from which the above-mentioned unsaturated five-membered ring or the unsaturated five-membered ring to which the electron-donating organic group 1 is bonded include cyclopentadiene, dicyclopentadiene, norbornene, and derivatives thereof. The oxygen-absorbing compound can have an unsaturated five-membered ring derived from one or more of these selected from the group consisting of these. The concentration of the unsaturated five-membered ring in the oxygen absorbing compound is not particularly limited, but is preferably 1% by mass or more and 70% by mass or less, and more preferably 5% by mass or more and 60% by mass or less. If the concentration is lower than the above range, the oxygen absorbing property is likely to be insufficient. It is difficult to achieve this, and the balance between the physical properties is easily compromised.
[0060] (Electron-donating organic group 1) Specific examples of the organic group 1 include an alkyl group, an alkylene group, a cyclic alkylene group, etc. Among these, a cyclic alkylene group is preferable, and one which constitutes an aliphatic bicyclic alkylene group together with the unsaturated five-membered ring is more preferable. Specific examples of the cyclic alkylene group include a cyclopropylene group, a cyclobutylene group, a cyclopentylene group, a cyclohexylene group, a cycloheptylene group, a cyclooctylene group, etc. Among these, a cyclopentylene group is more preferable.
[0061] (Electron-withdrawing organic group) Specific examples of the electron-withdrawing group include a phenyl group, a phenylene group, a carbonyl group, and a halogen. Indenes and coumarones in which only these electron-withdrawing groups are bonded to an unsaturated five-membered ring have a low electron density in the carbon-carbon double bond portion of the unsaturated five-membered ring, which reduces the reactivity with oxygen and results in low oxygen absorption.
[0062] (Functional group having active hydrogen) A functional group having an active hydrogen is chemically reactive. Specific examples of the functional group having an active hydrogen include a primary amino group, a secondary amino group, an aliphatic hydroxyl group, an aromatic hydroxyl group, an imino group, a carboxyl group, a urethane group, and a urea group. Among these, a primary amino group, a secondary amino group, an aliphatic hydroxyl group, and an aromatic hydroxyl group are preferred, and an aliphatic hydroxyl group is more preferred.
[0063] (organic group 2) Organic group 2 is a monovalent and / or divalent or higher group that substitutes an active hydrogen of a functional group having an active hydrogen on the five-membered ring or organic group 1 and is bonded to the five-membered ring or organic group 1. When there are two or more such unsaturated five-membered rings in one molecule, the unsaturated five-membered rings are bonded to each other via a structure in which the active hydrogen of a functional group having an active hydrogen is substituted with a divalent or higher organic group 2. As a specific example, a functional group having an active hydrogen on organic group 1 reacts with an isocyanate group of an isocyanate compound having a structural portion from which organic group 2 is derived, and the active hydrogen is substituted for organic group 2, resulting in bonding via a urethane group. By bonding the organic group 2, the oxygen absorbing compound can have two or more of the unsaturated five-membered rings in one molecule, and furthermore, when mixed with a resin or a resin composition to prepare a mixture, the compatibility, dispersibility, and reactivity can be improved.Furthermore, the mixture or the cured product of the mixture can be adjusted to be soft.
[0064] The organic group 2 may be an aliphatic group, an aromatic group, or may have both an aliphatic group and an aromatic group. The organic group 2 present in one molecule of the oxygen-absorbing compound may be of one type or of two or more types. The organic group 2 is preferably a group containing a structural portion derived from an isocyanate compound and / or a hydroxyl group-containing compound. Here, the structural portion derived from an isocyanate compound and / or a hydroxyl group-containing compound includes a structural portion derived from a reaction product of an isocyanate compound and a hydroxyl group-containing compound.
[0065] (Isocyanate compounds) Examples of the isocyanate-based compound from which the organic group 2 is derived include tetramethylene diisocyanate, hexamethylene diisocyanate, lysine diisocyanate, isopropyl alcohol, etc. Examples of the isocyanate include phoron diisocyanate, norbornane diisocyanate, xylylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, phenylene diisocyanate, diphenylether diisocyanate, hydrogenated diphenylmethane diisocyanate, polymethylene polyphenyl polyisocyanate, and their trimethylolpropane adducts, biuret forms, allophanate forms, isocyanurate forms (trimers), and various derivatives thereof. Among these, biuret forms of toluene diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate are preferred. In the present invention, one or more types selected from the group consisting of these isocyanate compounds can be used as the origin of the structural portion of the monovalent and / or divalent or higher hydrocarbon group. When two or more types are used, two types may be used in the same molecule of the oxygen-absorbing compound, or molecules of the oxygen-absorbing compound having different types may be mixed.
[0066] The number average molecular weight of the isocyanate compound is preferably 100 to 10,000, more preferably 160 to 5,000. If the number average molecular weight is smaller than the above range, it is likely to precipitate when mixed with a resin or a resin composition. If the number average molecular weight is larger than the above range, it is likely to require a large amount of dilution solvent to be contained when mixed with a resin or a resin composition because the viscosity of the mixture increases, making it difficult to obtain a thick film or layer, and coating suitability is likely to deteriorate.
[0067] (Hydroxy group-containing compound) The hydroxyl group-containing compound is a compound from which the above organic group 2 is derived, and has two or more hydroxyl groups. Examples of the hydroxyl group-containing compound include polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof, vinyl chloride-vinyl acetate copolymers, cellulose acetate resins, styrene-maleic acid ester copolymers, polyamide resins, polyimide resins, etc. Among these, compounds containing one or more selected from the group consisting of polyester polyols, poly(meth)acrylic acid ester polyols, polyether polyols, and urethane chain-extended polyols thereof, vinyl chloride-vinyl acetate copolymers, cellulose acetate resins, styrene-maleic acid ester copolymers, polyamide resins, and polyimide resins are preferred. The above-mentioned hydroxyl group compound has a hydroxyl group obtained by (co)polymerizing a raw material having a hydroxyl group, or by modifying the above-mentioned resin with a hydroxyl group-containing compound. In order to prevent odor generation, the hydroxyl group-containing compound is preferably one that does not have a double bond in the aliphatic chain of the main skeleton or one that has two hydroxyl groups. Compounds that have a hydroxyl group at the end are preferred because they are more readily available, but they do not have to be at the end. In the present invention, one or more types selected from the group consisting of these can be used as the hydroxyl group-containing compound from which the organic group 2 is derived. When two or more types are used, two types may be used in the same molecule of the oxygen-absorbing compound, or molecules of the oxygen-absorbing compound having different types may be mixed. The number average molecular weight of the hydroxyl group-containing compound is preferably 500 to 10,000, more preferably 750 to 5,000, and even more preferably 1,000 to 3,000. If the number average molecular weight is smaller than the above range, it is likely to precipitate when mixed with a resin or a resin composition. If the number average molecular weight is larger than the above range, it is likely to require a large amount of dilution solvent to be contained when mixed with a resin or a resin composition because the viscosity of the mixture increases, making it difficult to obtain a thick film or layer, and coating suitability is likely to deteriorate.
[0068] Polyhydric alcohols Polyhydric alcohols are monomers having two or more hydroxyl groups. Specific examples of polyhydric alcohols include diols such as ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,3-butanediol, 1,6-hexanediol, cyclohexanedimethanol, 1,8-octanediol, 1,9-nonanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 2-methyl-1,3-propanediol, 2,2,4-trimethyl-1,3-pentanediol, 2,4-diethyl-1,5-pentanediol, 1,12-octadecanediol, and 2,2'-oxydiethanol, as well as glycerin, mannitol, and sorbitol. Among the above, ethylene glycol is preferred in terms of oxygen absorption.
[0069] Polyolefin polyol The polyolefin polyol is a polyolefin resin having two or more hydroxyl groups. Specific examples of polyolefin polyols include those whose main skeleton is a polyolefin such as polyethylene, polypropylene, polybutylene, polybutadiene, hydrogenated polybutadiene, polyisoprene, hydrogenated polyisoprene, ethylene-vinyl acetate copolymer, ethylene-ethyl (meth)acrylate copolymer, ethylene-(meth)acrylic acid copolymer, and ethylene-propylene copolymer, and which have a hydroxyl group. Among these, those having an ethylene-vinyl acetate copolymer or hydrogenated polyisoprene as the main skeleton are particularly preferred.
[0070] Polyether polyol Polyether polyol is a polyether resin having two or more hydroxyl groups. Polyether polyols are obtained, for example, by dehydration condensation of the above-mentioned polyhydric alcohols or polyolefin polyols, and have a polyether structure in the main skeleton and a hydroxyl group. Specific examples of polyether polyols include polyalkylene ether diols such as diethylene glycol, triethylene glycol, dipropylene glycol, polyethylene ether diol, polypropylene ether diol, polybutylene ether diol, and glycerin-modified polyether polyols. Among these, polyalkylene ether diols are preferred, and polypropylene ether diol is particularly preferred.
[0071] Polyester polyol The polyester polyol is a polyester resin having two or more hydroxyl groups. The polyester polyols are obtained, for example, by esterification reaction between various polyvalent carboxylic acids or derivatives thereof and the above-mentioned polyhydric alcohols, polyolefin polyols, polyether polyols, etc., and have a polyester structure in the main skeleton and hydroxyl groups. Specific examples of polycarboxylic acids include adipic acid, phthalic acid, isophthalic acid, terephthalic acid, maleic acid, fumaric acid, succinic acid, oxalic acid, malonic acid, pimelic acid, azelaic acid, sebacic acid, suberic acid, glutaric acid, 1,4-cyclohexanedicarboxylic acid, and trimellitic acid. Derivatives of these polycarboxylic acids include esters, acid anhydrides, and acylation products. Among the above, polyester polyols using two or more kinds of polyhydric alcohols and two or more kinds of polyvalent carboxylic acids in combination are preferred in order to reduce crystallinity.
[0072] Polycarbonate polyol Polycarbonate polyol is a polycarbonate resin having two or more hydroxyl groups. Polycarbonate has a polyol-derived portion in the main skeleton, and this polyol-derived portion can be any of the above-mentioned polyhydric alcohols, polyolefin polyols, polyether polyols, polyols, etc. It may be derived from an ester polyol or the like. Among these, polycarbonate polyols using two or more kinds of polyhydric alcohols in combination are preferred in order to reduce crystallinity.
[0073] Poly(meth)acrylic acid ester polyol The poly(meth)acrylate polyol is a (meth)acrylate (co)polymer having two or more hydroxyl groups. Poly(meth)acrylic acid ester polyol can be obtained, for example, by using a hydroxyl group-containing monomer such as 2-hydroxyethyl methacrylate or a (meth)acrylic acid ester having a hydroxyl group synthesized from one (meth)acrylic acid or a derivative thereof and one diol, and polymerizing the hydroxyl group-containing monomer with itself or copolymerizing it with a (meth)acrylic acid ester not having a hydroxyl group. As the diol used in synthesizing the (meth)acrylic ester having a hydroxyl group, the above-mentioned diols, polyolefin polyol, polyether polyol, etc. can be used. Among these, a poly(meth)acrylic acid ester copolymer using 2-hydroxyethyl methacrylate is preferred.
[0074] Phenoxy resin Phenoxy resin is a resin obtained by reacting a polyhydric phenol compound with a polyhydric epoxy compound, and has a structure in which an aliphatic hydroxyl group is generated at the bond formed by reaction between an aromatic hydroxyl group and an epoxy group. As the phenoxy resin, those obtained by reacting a bisphenol with a diglycidyl etherified bisphenol are readily available and are common. Examples of the polyhydric phenol compound include bisphenol A and bisphenol F, and examples of the polyfunctional epoxy compound include bisphenol A diglycidyl ether and bisphenol F diglycidyl ether. Among these, phenoxy resins using bisphenol A are preferred. The terminal of the phenoxy resin may be an aromatic hydroxyl group or an epoxy group.
[0075] · Urethane chain-extended polyol The urethane chain-extended polyol is a polyol having two or more hydroxyl groups, which is obtained by extending the above-mentioned hydroxyl group-containing compound with a urethane chain. The urethane chain-extended polyol can be obtained, for example, by polymerizing the above-mentioned various hydroxyl group-containing compounds with the above-mentioned isocyanate-based compounds to extend the urethane chain. If necessary, diamines or amino alcohols may be used in combination for polymerization. Among the above, urethane chain-extended polyols obtained by reacting the above-mentioned various hydroxyl group-containing compounds having hydroxyl groups at both ends with a diisocyanate compound are preferred.
[0076] (Specific examples of oxygen absorbing compounds) Specific examples of the oxygen-absorbing compound are given below. 3a,4,5,6,7,7a-Hexahydro-4,7-methano-1H-indenol represented by formula (1), 3a,4,5,6,7,7a-hexahydro-4,7-methano-1H-indenamine represented by formula (1-b), and 3a,4,5,6,7,7a-hexahydro-4,7-methano-1H-inden-1-ol represented by formula (1-c) are examples of oxygen absorbing compounds each having one unsaturated five-membered ring and one organic group 1, and the organic group 1 has a hydroxyl group or an amino group as a functional group having active hydrogen. [ka] [ka] [ka]
[0077] The oxygen absorbing compound represented by formula (2) is, for example, a compound having a hydroxyl group, which is a functional group having an active hydrogen on organic group 1 of the oxygen absorbing compound represented by formula (1), and an isocyanate compound R 1 (NCO) a The isocyanate group of the hydroxyl group is reacted with the active hydrogen of the hydroxyl group to replace the a number of unsaturated five-membered rings and the organic group 1 to form R 1 It is an oxygen absorbing compound that can be obtained by bonding via [ka] (In the formula, a is a number of 1 or more, and R 1 is an organic group having one or more carbon atoms, containing at least an alkylene and / or phenylene structure, and further containing a structure derived from one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof.
[0078] The oxygen absorbing compound represented by formula (5) is a compound represented by formula (2) in which a=2 and R 1 For example, the isocyanate compound OCN-R 4 -NCO and hydroxyl group-containing compounds HO-R 5 The oxygen absorbing compound is a group derived from -OH and containing a structural part generated by the reaction of the two. [ka] (In the formula, f is a number equal to or greater than 0, and R 4 and R 5Each of the above is an organic group having one or more carbon atoms, containing at least an alkylene and / or phenylene structure, and further may contain a structure derived from one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof.
[0079] The oxygen-absorbing compound represented by formula (3) may be, for example, 1 is derived from an isocyanate compound and a hydroxyl group-containing compound, contains a structural part formed by the reaction of the two, and contains hydroxyl groups as a result of residual excess hydroxyl groups or chemical modification. [ka] (In the formula, b and c are each a number equal to or greater than 1; R 2 is an organic group having one or more carbon atoms, containing at least an alkylene and / or phenylene structure, and further containing a structure derived from one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof.
[0080] The oxygen-absorbing compound represented by formula (4) may be, for example, 1 is derived from an isocyanate compound and a hydroxyl group-containing compound, contains a structural part generated by the reaction of the two, and contains an isocyanate group as a result of residual excess isocyanate groups or chemical modification. [ka] (wherein, d and e are each a number equal to or greater than 1; R 3is an organic group having one or more carbon atoms, containing at least an alkylene and / or phenylene structure, and further containing a structure derived from one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof.
[0081] [Oxidation promotion catalyst] The oxidation-promoting catalyst is a compound that promotes the action of the oxygen-absorbing compound absorbing oxygen molecules and being oxidized. Examples of the oxidation-promoting catalyst include peroxides and compounds containing cations made of transition metals. Specific examples of the peroxide include hydrogen peroxide. The compound containing a cation made of a transition metal is preferably a metal soap made of a transition metal-containing compound capable of releasing a cation or complex of a transition metal atom and an anion or ligand made of a fatty acid. As the transition metal, cobalt, manganese, iron, nickel, copper, etc. are preferred, and as the anion or ligand, anion or ligand formed of stearic acid, naphthenic acid, octylic acid, acetylacetonate, etc. are preferred. The oxidation-promoting catalyst may be a metal soap formed by combining a cation made of one or more transition metals selected from the group consisting of the above transition metals with an anion made of one or more fatty acids selected from the group consisting of the above long-chain fatty acids. Specific compounds include cobalt octylate, cobalt acetylacetone (II), cobalt acetylacetone (III), manganese acetylacetone (III), and iron acetylacetone (III).
[0082] [Denaturant] The modifier is a compound having a functional group that reacts with the oxygen absorbing compound when the oxygen absorbing compound has a functional group, and various reactive monomers and resins can be used. By including a modifier in the oxygen-absorbing coating composition, it is possible to bond the oxygen-absorbing compound to other components in the oxygen-absorbing coating composition, to adjust the content of the oxygen-absorbing compound in the oxygen-absorbing coating composition, and to adjust the hardness of the cured product of the oxygen-absorbing coating composition.
[0083] For example, when the oxygen absorbing compound has a hydroxyl group or an isocyanate group, a modifying agent made of an isocyanate compound and / or a hydroxyl group-containing compound can be used. When the oxygen-absorbing coating composition is a urethane-based composition, the equivalent ratio NCO / OH of the oxygen-absorbing coating composition is preferably 0.5 or more and 8 or less. If it is less than the above range, the curing of the oxygen-absorbing coating composition may be insufficient, and sufficient lamination strength (adhesive strength) may not be obtained, whereas if it is greater than the above range, the pot life of the oxygen-absorbing coating composition may be too short.
[0084] (Isocyanate compounds for use as modifiers) The isocyanate compound for the modifier can be the isocyanate compound used in the synthesis of the oxygen absorbing compound, and can be any of aromatic isocyanate, aliphatic isocyanate, and urethane chain-extended isocyanate thereof. In addition, in order to harden the oxygen absorbing coating composition, it is preferable to have two or more isocyanate groups in one molecule. However, it can also be used in combination with an isocyanate compound having one isocyanate group in one molecule within a range that does not hinder the sufficient effect of the oxygen absorbing coating composition. As the isocyanate compound having two or more isocyanate groups in one molecule, a biuret form of hexamethylene diisocyanate is particularly preferred.
[0085] Specific examples of the isocyanate compounds include tetramethylene diisocyanate, hexamethylene diisocyanate, lysine diisocyanate, isophorone diisocyanate, norbornane diisocyanate, xylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, phenylene diisocyanate, Examples of the isocyanate include toluene diisocyanate, diphenyl ether diisocyanate, polymethylene polyphenyl polyisocyanate, and their trimethylolpropane adducts, biuret forms, allophanate forms, isocyanurate forms (trimers), and various derivatives thereof. Among these, biuret forms of toluene diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate are preferred.
[0086] (Hydroxyl-containing compounds for use as modifiers) The hydroxyl group-containing compound for the modifier can be the hydroxyl group-containing compound used in the synthesis of the oxygen absorbing compound, and can be any of aromatic hydroxyl group-containing compounds, aliphatic hydroxyl group-containing compounds, and urethane chain-extended polyols thereof.In addition, in order for the oxygen absorbing coating composition to harden, it is preferable to have two or more hydroxyl groups in one molecule.However, it can also be used in combination with a hydroxyl group-containing compound having one hydroxyl group in one molecule within a range that does not hinder the sufficient effect of the oxygen absorbing coating composition. As the hydroxyl group-containing compound having two or more hydroxyl groups in one molecule, either an aromatic hydroxyl group-containing compound or an aliphatic hydroxyl group-containing compound can be used, and either an alcohol-based or a phenol-based compound can be used. As the hydroxyl group-containing compound having two or more hydroxyl groups in one molecule, polyalkylene ether diols and urethane chain-extended polyols of polyalkylene ether diols are particularly preferred.
[0087] [Dilution solvent] The dilution solvent is not particularly limited as long as it can uniformly dissolve or disperse the oxygen-absorbing compound and the oxidation-promoting catalyst, make the oxygen-absorbing coating agent composition uniform, and is suitable for coating. For example, an ester-based dilution solvent, a ketone-based dilution solvent, a hydrocarbon-based dilution solvent, etc. can be used. Specific examples of the ester-based diluent solvent include ethyl acetate, butyl acetate, etc., specific examples of the ketone-based diluent solvent include methyl ethyl ketone, etc., and specific examples of the hydrocarbon-based diluent solvent include toluene, etc. Among these, ethyl acetate is easy to use and is preferable.
[0088] [Various additives] The oxygen-absorbing coating composition may contain various additives as required. For example, curing accelerators, curing regulators for extending the pot life, antioxidants for suppressing a decrease in oxygen absorbing properties during storage or use of the oxygen absorbing coating composition and before the contents are placed in a package, adhesion aids, tackifiers, leveling agents, ultraviolet absorbers, defoamers, coloring pigments, and extender pigments may also be added.
[0089] (Cure accelerator) The curing accelerator can be used without any particular limitation as long as it accelerates the curing reaction of the oxygen-absorbing coating agent composition. Specific examples of the curing accelerator include metal-containing compounds such as dibutyltin dilaurate, dibutyltin diacetate, dioctyltin dilaurate, dibutyltin dimaleate, tetrabutyl titanate, and tetraisopropyl titanate, and tertiary amines such as 1,8-diaza-bicyclo(5,4,0)undecene-7, 1,5-diazabicyclo(4,3,0)nonene-5, and triethanolamine. One or more types selected from the group consisting of these can be used.
[0090] (hardening regulator) When the pot life of the oxygen-absorbing coating composition is shortened due to the oxidation-promoting catalyst contained therein, the pot life can be extended by using a cure regulator in combination. Specific examples of the hardening regulator include phosphoric acids, such as orthophosphoric acid, metaphosphoric acid, Examples of the polyphosphoric acid and its ester derivatives are mentioned, and one or more selected from the group consisting of these can be used. The amount of the reaction regulator added is preferably 200 ppm or more and 400 ppm or less based on the resin component of the oxygen-absorbing coating composition. If the amount is less than the above range, it is difficult to obtain the effect of extending the pot life, and if the amount is more than the above range, there is a risk that the curing of the oxygen-absorbing coating composition is inhibited.
[0091] (Antioxidants) The oxygen-absorbing coating composition can contain an antioxidant in order to suppress deterioration of oxygen absorption properties during storage or use of the oxygen-absorbing coating composition, and also in processes before a package produced using the oxygen-absorbing coating composition contains contents, and to maintain high oxygen absorption properties after the contents are contained. Specific examples of the antioxidant include phenols, lactones, thioethers, gallic acids, ascorbic acid, erythorbic acid, catechin, dibutylhydroxytoluene, tocopherol, citric acid, butylhydroxyanisole, phosphite, hindered amines, and aromatic amines. One or more selected from the group consisting of these antioxidants can be used. In addition, when it is assumed that heat or light is used as a trigger for expressing oxygen absorbing ability, it is preferable to use an antioxidant having low heat resistance and light resistance, such as ascorbic acid or tocopherol, and it is not preferable to use an antioxidant having high heat resistance and light resistance, such as a phenol-based antioxidant. The amount of the antioxidant added is preferably 10 ppm or more and 10000 ppm or less relative to the oxygen absorbing compound. If the amount is less than the above range, the antioxidant effect is likely to be insufficient, and if the amount is more than the above range, there is a risk that the oxygen absorbing ability will decrease.
[0092] (Adhesion aid) As an adhesion aid for improving adhesive strength, a silane coupling agent is preferred. Examples of the silane coupling agent include γ-glycidoxypropyltrialkoxysilane, γ-methacryloxypropyltrialkoxysilane, γ-glycidoxypropylmethyldialkoxysilane, β-(3,4-epoxycyclohexyl)ethyltrialkoxysilane, γ-aminopropyltrialkoxysilane, γ-aminopropylmethyldialkoxysilane, N-(β-aminoethyl)-γ-aminopropyltrialkoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldialkoxysilane, N-butyl-3-amino-2-methylpropyltrialkoxysilane, γ-mercaptopropyltrialkoxysilane, and γ-mercaptopropylmethyldialkoxysilane. The alkoxy group is preferably a methoxy group or an ethoxy group, and one or more selected from the group consisting of these can be used.
[0093] (tackifier) Examples of the tackifier include paraffin wax, polyethylene wax, rosin, rosin glycerin ester, terpene, and alkylphenol. One or more types selected from the group consisting of these can be used.
[0094] (Leveling agent) The leveling agent may be an acrylic polymer-based agent, a modified silicone-based agent, an acetylene diol-based agent, or the like. One or more types selected from the group consisting of these may be used.
[0095] (UV absorber) Examples of the ultraviolet absorbing agent include benzotriazoles, hydroxyphenyltriazines, and hindered amines. One or more types selected from the group consisting of these may be used. It can be used.
[0096] (Antifoaming agent) The antifoaming agent may be a surfactant, polyether-modified silicone oil, or the like, and one or more selected from the group consisting of these may be used.
[0097] (Color pigments) Examples of color pigments include organic pigments such as anthraquinone, diketopyrrolopyrrole, perylene maroon, carbon black, dioxazine, perylene, benzimidazolone, isoindolinone, isoindoline, phthalocyanine, and indanthrene, and inorganic pigments such as yellow iron oxide, red iron oxide, azomethine copper complex, titanium oxide, and silicon oxide. One or more types selected from the group consisting of these can be used.
[0098] (Extender pigment) The extender pigment is a white or colorless pigment that is used as an extender or as an adjuster for coloring power, gloss, strength, usability, etc. Specific examples include inorganic pigments such as barium sulfate, barium carbonate, calcium carbonate, magnesium oxide, magnesium carbonate, magnesium hydroxide, barium titanate, calcium hydroxide, calcium sulfite, calcium sulfate, calcium oxide, calcium silicate, titanium oxide, silica, zeolite, and talc, and one or more types selected from the group consisting of these can be used.
[0099] <<Method for preparing oxygen-absorbing coating composition>> The oxygen-absorbing coating composition can be produced by mixing all of the components, such as the oxygen-absorbing compound, the oxidation-promoting catalyst, and, if necessary, the modifier, the dilution solvent, various additives, etc. Alternatively, the oxygen-absorbing coating composition can be produced by mixing the oxygen-absorbing compound, the oxidation-promoting catalyst, and, if necessary, the modifier, the dilution solvent, various additives, etc., with an existing coating composition. The method for carrying out the above mixing and the order in which the components are mixed are not particularly limited, and the method and mixing order used in preparing a general coating composition can be applied. Specific mixing methods include a method of dissolving in a solvent and mixing, and a method of melt-kneading. In this case, it is preferable to adjust the heating temperature in order to increase the solubility or dispersibility.
[0100] <<Method of using the oxygen-absorbing coating composition>> There is no particular limitation on the method of using the oxygen-absorbing coating composition, and any method for using the composition as a general coating agent can be used. For example, the coating layer can be formed by applying once or multiple times using a conventionally known method such as roll coating, spray coating, spin coating, dipping, brush coating, bar coating, or applicator. When forming a coating layer using the oxygen-absorbing coating composition, the coating amount is 2 to 10 g / m 2 is preferable, and 3 to 7 g / m 2 If the amount is less than the above range, sufficient oxygen absorbency may not be obtained, whereas if the amount is more than the above range, the oxygen absorbency does not change significantly, leading to a cost disadvantage, which is not preferable.
[0101] The laminate obtained by forming a coating layer using the oxygen-absorbing coating composition is preferably aged at 20° C. or higher and 50° C. or lower for 2 days or higher and 5 days or lower. In addition, in order not to decrease the oxygen absorption property of the laminate, it is preferable to carry out the aging at a temperature as low as possible or in an inert gas atmosphere. When storing the produced laminate, it is preferable to store it at 10° C. or below or in an inert gas atmosphere in order not to decrease the oxygen absorbing property of the laminate.
[0102] <About objects that can be coated> There are no particular limitations on the objects that can be coated with the oxygen-absorbing coating composition, and examples of the objects that can be coated with the oxygen-absorbing coating composition include resin molded products, resin films, paper, metals, metal foils, inorganic vapor deposition film surfaces, and inorganic oxide vapor deposition film surfaces.
[0103] Specific examples of resins for the resin film include polyester-based resins such as polyethylene terephthalate (PET), polyamide-based resins such as various nylons, polyethylene-based resins, polypropylene-based resins, cyclic polyolefin-based resins, polystyrene-based resins, polyolefin-based resins such as acrylonitrile-styrene copolymers (AS resins), acrylonitrile-butadiene-styrene copolymers (ABS resins), and polybutene-based resins, polyvinyl chloride-based resins, polycarbonate-based resins, polyimide-based resins, polyamideimide-based resins, diallyl phthalate-based resins, silicone-based resins, polysulfone-based resins, polyphenylene sulfide-based resins, polyethersulfone-based resins, polyurethane-based resins, cellulose-based resins, poly(meth)acrylic resins, polyvinylidene chloride-based resins, acetal-based resins, and fluorine-based resins.
[0104] Specific examples of paper include, for example, strong sizing bleached or unbleached paper base materials for paper layers, or paper base materials such as pure white roll paper, kraft paper, paperboard, coated paper, processed paper, milk base paper, barrier coated paper, and the like. Specific examples of the metal foil include aluminum foil, copper foil, and stainless steel foil. A specific example of the inorganic material of the inorganic vapor deposition layer is aluminum. Specific examples of inorganic oxides in the inorganic oxide vapor deposition layer include silica, alumina, indium tin oxide, zinc oxide, tin oxide, titanium oxide, zirconium oxide, vanadium oxide, barium oxide, chromium oxide, silicon nitride, silicon carbide, etc. Among these, silica and alumina are preferred.
[0105] <Sealant layer> The sealant layer may be composed of a single layer, or may be composed of two or more layers having the same or different compositions. The sealant layer is a layer for heat sealing when forming the oxygen-absorbing coated package, and therefore preferably contains a resin having heat sealability. The sealant layer may be laminated over the entire surface of the laminate, or may be laminated only over a portion of the surface, for example, a portion to be heat-sealed, in the form of a part coat or part laminate.
[0106] The sealant layer may contain any additives within the range that does not significantly impair the effects of the present invention. Examples of the additives include various resin additives that are generally used to adjust the moldability, productivity, and various physical properties of the resin film, such as antiblocking agents, slip agents, antioxidants, pigments, flow control agents, flame retardants, fillers, ultraviolet absorbers, and surfactants. The thickness of the sealant layer is preferably 1 μm to 150 μm, more preferably 5 μm to 70 μm, and when the sealant layer is a part coat using a heat sealing agent, it is further preferably 5 μm to 7 μm.
[0107] [Heat-sealable resin] Resins having heat sealability include polyolefin resins, acid-modified polyolefin resins obtained by modifying polyolefin resins with an unsaturated carboxylic acid or its anhydride, such as acrylic acid, methacrylic acid, maleic acid, maleic anhydride, fumaric acid, or itaconic acid, through graft polymerization or copolymerization, polyvinyl acetate resins, and poly(meth)acrylic resins. Resins such as polyvinyl chloride resins and the like can be used. These resins can be used alone or in combination. Of the above resins, polyolefin resins are preferred from the standpoint of adhesion and production costs, and of the polyolefin resins, low density polyethylene, linear low density polyethylene, etc. are particularly preferred.
[0108] (Polyolefin resin) Specific examples of polyolefin resins include polyethylene, low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, ethylene-α-olefin copolymers polymerized using a metallocene catalyst, polypropylene, ethylene-vinyl acetate copolymers, ethylene-vinyl alcohol copolymers, ionomer resins, ethylene-acrylic acid copolymers, ethylene-ethyl acrylate copolymers, ethylene-methacrylic acid copolymers, ethylene-methyl methacrylate copolymers, ethylene-propylene copolymers, methylpentene (co)polymers, butene (co)polymers, ethylene-acrylic acid copolymers, ethylene-methacrylic acid copolymers, and cyclic olefin (co)polymers such as polynorbornene. The copolymers may be random or block copolymers.
[0109] Polyolefin resins are classified into, for example, polyethylene resins and polypropylene resins depending on the skeleton of the monomer used in the synthesis of the polyolefin, and may be copolymers. In the present invention, the term "polyethylene resin" is added as a general term for various types, and for example, polyethylene resin is also used as a general term for various types of polyethylene. Polyolefins produced by polymerizing α-olefins such as ethylene, propene, 1-butene, 1,3-butadiene, and 1-hexene as raw materials are called polyethylene-based resins, polypropylene-based resins, polybutylene-based resins, polybutadiene-based resins, polyhexene-based resins, and the like, respectively. Common polymerization methods include, for example, a high-pressure method for low-density polyethylene, and a low-pressure polymerization method (gas phase polymerization using a Ziegler-Natta catalyst or liquid phase polymerization using a metallocene catalyst), slurry method, solution method, gas phase polymerization method, etc. for linear low-density polyethylene.
[0110] The raw material polyolefin resin for the heat-sealable polyolefin resin or acid-modified polyolefin resin may be a plant-derived polyolefin resin, although a fossil fuel-derived polyolefin resin may also be used in combination. By using plant-derived polyolefin resins, the environmental impact can be reduced. The plant-derived resin can be selected with an appropriate density and MFR depending on the physical properties of the fossil fuel-derived resin used in combination and the conditions of use of the laminate. The content of the plant-derived polyolefin resin in the sealant layer is preferably 40% by mass or more and 100% by mass or less. If it is less than the above range, the effect of reducing the environmental load is reduced. When the sealant layer has a multi-layer structure, the sealant layer may have a layer containing a plant-derived polyolefin resin and a layer not containing a plant-derived polyolefin resin. For example, it is preferable that the outer surface layer that is the outermost surface of the laminate does not contain a plant-derived polyolefin resin. Furthermore, when the sealant layer has a multi-layer structure of three or more layers, it is preferable that the layers on both surfaces of the sealant layer do not contain a plant-derived polyolefin resin, and the inner layer contains a plant-derived polyolefin resin.
[0111] Polyolefin resins are classified into fossil fuel-derived polyolefin resins and plant-derived polyolefin resins according to the origin of the raw material monomer. (Fossil fuel-derived polyolefin resin) In the present invention, the fossil fuel-derived polyolefin resin is a polyolefin resin that does not use a raw material monomer derived from a plant, but uses a raw material monomer obtained by pyrolysis of naphtha obtained from a fossil fuel as in the conventional method. (Plant-derived polyolefin resin) In the present invention, "plant-derived" means that it contains carbon derived from a plant raw material, for example, it means that it is produced using a compound obtained from a plant as a raw material. In a method for producing a plant-derived polyolefin resin, for example, first, sugar liquid or starch obtained from plants such as sugar cane, corn, or sweet potato is fermented by a microorganism such as yeast to produce bioethanol according to a conventional method, and this is then heated in the presence of a catalyst to obtain ethylene and α-olefins (1-butene, 1-hexene, etc.) through an intramolecular dehydration reaction or the like. Next, these are used as raw monomers for polymerization, and are polymerized in the presence of a conventional catalyst in the same manner as in the production of fossil fuel-derived polyolefin resins, to produce plant-derived polyolefin resins. The catalyst and polymerization method used in polymerization are the same as those used in the production of fossil fuel-derived polyolefin resins. As a part of the raw material monomers for polymerization or copolymerization monomers, those derived from fossil fuels can also be used in combination, if necessary.
[0112] [Method of forming sealant layer] The method for forming the sealant layer is not particularly limited, and any conventionally known method for laminating a sealant layer can be used. A sealant film consisting of one or more layers for the sealant layer may be prepared in advance, and the sealant film may be laminated by adhering it to other layers constituting the laminate via an adhesive, etc. The sealant film may be prepared by melt-extruding one or more resin compositions and forming them into a film by an inflation method, or by melt-extruding onto a roll and constricting it by an extrusion method using a T-die molding or the like to form a film.
[0113] Here, it is preferable to subject one side of the prepared sealant film to a corona treatment, and then laminate the film by adhering the corona-treated side to the side to be laminated. Alternatively, the resin composition for forming the sealant layer may be melted, melt (co)extruded, and poured onto the layers to be laminated, and a sealant layer consisting of one or more layers may be laminated onto the other layers that make up the laminate by an extrusion method using a T-die molding method using a feed block method or a multi-manifold method. Alternatively, a heat sealant containing a water-based or organic solvent may be applied onto the layer to be laminated and dried to form a sealant layer consisting of one or more layers. In either method, a multi-layer sealant film or a sealant layer can be prepared by (co)melt extrusion or coating / drying using resin compositions of the same or different compositions. When the sealant layer is laminated on a part of a surface rather than the entire surface, part coating using the above-mentioned heat sealant is preferred.
[0114] ≪Base material layer≫ The material of the substrate layer may be a commonly known and commonly used material having excellent mechanical, physical, chemical, and other properties, particularly strength, toughness, and heat resistance. Specifically, various resin films and / or paper substrates may be used, and a resin film and a paper substrate may be used in combination. The substrate layer may be composed of one layer, or may be composed of two or more layers of the same or different composition laminated by any lamination means. The thickness of the base layer can be appropriately set by those skilled in the art, but for the purpose of imparting appropriate strength and stiffness to the laminate, the thickness of the base layer is preferably 5 μm to 100 μm, and more preferably 10 μm to 50 μm. m is more preferable, and 15 to 25 μm is even more preferable. The substrate layer may be integrated with an oxygen barrier layer in advance, and may be, for example, a resin film with an inorganic vapor deposition layer, or a barrier paper such as a paper substrate with an oxygen barrier layer.
[0115] (Resin film) Specific examples of resins constituting the resin film include polyester-based resins such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polyethylene naphthalate (PNT), polyethylene-based resins (low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), etc.), polyolefin-based resins such as polypropylene-based resins, polybutene-based resins, and cyclic polyolefin resins, polyamide-based resins such as nylon, polyaramid-based resins, polyimide-based resins, polyamideimide-based resins, polyurethane-based resins, and polysulfone-based resins. Examples of the resin films include resin films made from tough thermoplastic resins such as sulfone-based resins, such as polyphenylene sulfide-based resins and polyethersulfone-based resins, polycarbonate-based resins, polyacetal-based resins, cellulose-based resins, polyvinyl chloride, polyvinylidene chloride, nitrile-based resins, such as acrylonitrile-styrene copolymers (AS resins) and acrylonitrile-butadiene-styrene copolymers (ABS resins), poly(meth)acrylic resins, polystyrene-based resins, polyarylphthalate resins, silicone-based resins, fluorine-based resins, and others.
[0116] The resin film may be either an unstretched film or a uniaxially or biaxially stretched film. In the present invention, preferred are biaxially oriented polyethylene terephthalate films, biaxially oriented nylon films, polyacrylonitrile films, ethylene-vinyl alcohol copolymer films, non-oriented polypropylene (CPP), low-density polyethylene (LDPE) films, linear low-density polyethylene (LLDPE) films, and the like, which can be bonded by heat sealing or adhesive, and more preferably biaxially oriented PET films and biaxially oriented nylon films.
[0117] (Paper base material) Various known paper substrates (base papers) can be used, such as strong sizing bleached or unbleached paper, pure white roll paper, fine paper, medium quality paper, coated paper, one-sided glossy paper, kraft paper, one-sided glossy kraft paper, bleached kraft paper, glassine paper, paperboard, processed paper, white paperboard, liner, milk base paper, and barrier coated paper. The paper base material has a basis weight of 25 g / m 2 More than 400g / m 2 The following is preferred: 30 g / m 2 More than 110g / m 2 The following are more preferable: When the basis weight is within this range, the sheet is suitable for packaging applications such as packaging materials for food, containers, cups, etc., and is particularly suitable for soft packaging applications. The paper substrate may be a laminate of multiple layers of these papers.
[0118] In addition, in order to improve adhesion to adjacent layers, the surface of the paper substrate may be subjected to physical surface treatments such as corona discharge treatment, ozone treatment, plasma treatment, glow discharge treatment, sandblasting treatment, etc., or chemical surface treatments such as chemical treatment using chemicals or oxidation treatment, if necessary. Specific examples of chemicals used in the chemical treatment include oxidized starch, hydroxyethyl etherified starch, enzyme-modified starch, polyacrylamide, polyvinyl alcohol, surface sizing agents, water-resistant agents, water-retaining agents, thickeners, lubricants, etc., and these can be used alone or in combination of two or more types.
[0119] The above-mentioned various agents can be used by mixing with pigments. Pigments include kaolin, clay, engineered kaolin, delaminated clay, ground calcium carbonate, light calcium carbonate, mica, talc, titanium dioxide, barium sulfate. Inorganic pigments such as silica, calcium sulfate, zinc oxide, silicic acid, silicates, colloidal silica, and satin white, and organic pigments such as solid, hollow, and core-shell types can be used alone or in combination of two or more. The method for treating the surface of the paper substrate is not particularly limited, but known coating devices such as a rod metering size press, a pond type size press, a gate roll coater, a spray coater, a blade coater, and a curtain coater can be used.
[0120] The method for producing the paper base material (papermaking) is not particularly limited, and the paper base material can be produced by making paper using a known Fourdrinier former, on-top hybrid former, gap former machine, etc., using an acidic papermaking, neutral papermaking, or alkaline papermaking method. The paper base material is made from pulp and may contain fillers, various auxiliary agents, and the like. Examples of pulp that can be used include chemical pulps such as bleached hardwood kraft pulp (LBKP), unbleached hardwood kraft pulp (LUKP), bleached softwood kraft pulp (NBKP), unbleached softwood pulp (NUKP), sulfite pulp, and other such pulps; mechanical pulps such as stone-ground pulp and thermomechanical pulp; deinked pulp; and recycled paper pulp and other such wood fibers; and non-wood fibers obtained from kenaf, bamboo, hemp, and the like. One type may be used alone, or two or more types may be appropriately mixed and used. Among these, it is preferable to use chemical pulp or mechanical pulp made from wood fibers, and it is more preferable to use chemical pulp, because they are less likely to be mixed with foreign matter, less likely to discolor over time, have a high degree of whiteness, and provide a good surface feel when printed.
[0121] As the filler, known fillers can be used, specific examples of which include white carbon, talc, kaolin, clay, heavy calcium carbonate, light calcium carbonate, titanium oxide, zeolite, and synthetic resin fillers. As various additives, aluminum sulfate and various anionic, cationic, nonionic or amphoteric retention aids, drainage aids, paper strength agents, internal sizing agents, etc. may be used as necessary. Furthermore, dyes, fluorescent whitening agents, pH adjusters, defoamers, pitch control agents, slime control agents, etc. may also be added as necessary.
[0122] Furthermore, if necessary, plastic compounding agents and additives such as lubricants, crosslinking agents, antioxidants, ultraviolet absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, pigments, etc. may be added for the purpose of improving or modifying processability, heat resistance, weather resistance, mechanical properties, dimensional stability, oxidation resistance, slipperiness, release properties, flame retardancy, mildew resistance, electrical properties, strength, etc., and the like. The amount of these additives may be arbitrarily added depending on the purpose, within the range that does not adversely affect other performance properties.
[0123] ≪Printing layer≫ The printed layer visually presents design patterns such as letters, numbers, figures, symbols, pictures, patterns, etc. for the purpose of decoration, indication of contents, indication of expiration date, indication of manufacturer, seller, etc., and for imparting aesthetic appeal, and can form the desired design pattern. The printing layer can be provided, for example, on the surface of the paper base layer that will be the outer side of the package, using a conventionally known printing ink. The printing method is not particularly limited, and conventionally known methods such as gravure printing, flexographic printing, and screen printing can be used. The printing layer may be provided on the entire surface to be printed, or may be provided on only a part of it. In order to make the printed layer visible, it is preferable that when the package is formed, the printed layer be the outermost layer, or a layer that is more outer than the printed layer be transparent.
[0124] ≪Adhesive resin layer≫ An adhesive resin layer and an anchor coat layer may be included between the layers constituting the oxygen-absorbing coat laminate. The adhesive resin layer may be, for example, a layer (extruded resin layer) formed by a (co)extrusion lamination method in which an adhesive resin composition is melt-extruded, a T-die (co)extrusion method, or the like, or may be a layer (dry laminate layer) formed by dry lamination using a dry laminate adhesive.
[0125] If necessary, the surface of the adhesive resin layer, which is the laminated extruded resin layer, may be subjected to a physical surface treatment such as corona discharge treatment, ozone treatment, plasma treatment, glow discharge treatment, sandblasting treatment, etc., or a chemical surface treatment such as oxidation treatment using chemicals. Examples of the resin contained in the adhesive resin composition include polyolefin resins, acid-modified polyolefin resins obtained by acid-modifying polyolefin resins by graft polymerization or copolymerization with unsaturated carboxylic acids or their anhydrides such as acrylic acid, methacrylic acid, maleic acid, maleic anhydride, fumaric acid, itaconic acid, etc., polyvinyl acetate resins, poly(meth)acrylic resins, polyvinyl chloride resins, etc. These resins can be used alone or in combination.
[0126] Specific examples of polyolefin resins include polyethylene, low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, ethylene-α-olefin copolymers polymerized using a metallocene catalyst, polypropylene, ethylene-vinyl acetate copolymers, ethylene-vinyl alcohol copolymers, ionomer resins, ethylene-acrylic acid copolymers, ethylene-ethyl acrylate copolymers, ethylene-methacrylic acid copolymers, ethylene-methyl methacrylate copolymers, ethylene-propylene copolymers, methylpentene (co)polymers, butene (co)polymers, polyisoprene, ethylene-acrylic acid copolymers, ethylene-methacrylic acid copolymers, and cyclic olefin (co)polymers such as polynorbornene. The copolymers may be random or block copolymers. Polyolefin resins are classified into, for example, polyethylene resins and polypropylene resins depending on the skeleton of the monomer used in the synthesis of the polyolefin, and may be copolymers. In the present invention, the term "polyethylene resin" is added as a general term for various types, and for example, polyethylene resin is also used as a general term for various types of polyethylene. Polyolefins produced by polymerizing α-olefins such as ethylene, propene, 1-butene, 1,3-butadiene, and 1-hexene as raw materials are called polyethylene-based resins, polypropylene-based resins, polybutylene-based resins, polybutadiene-based resins, polyhexene-based resins, and the like, respectively.
[0127] The adhesive resin layer may contain additives such as antioxidants, ultraviolet absorbers, light stabilizers, antistatic agents, antiblocking agents, flame retardants, crosslinking agents, and colorants, as long as the additives do not impair the characteristics of the present invention. The thickness of the adhesive resin layer is not particularly limited, but in the case of an extruded resin, it is preferably 5 μm or more and 60 μm or less, and in the case of a dry lamination adhesive, it is preferably 0.1 g / m 2 More than 20g / m 2 By setting the thickness of the adhesive resin layer within the above numerical range, stable adhesive strength can be obtained. In addition, examples of the dry lamination adhesive that constitutes the adhesive resin layer formed by dry lamination include two-component curing urethane adhesives, polyester urethane adhesives, polyether urethane adhesives, acrylic adhesives, polyester adhesives, polyamide adhesives, polyvinyl acetate adhesives, epoxy adhesives, rubber adhesives, and others.
[0128] The anchor coat layer is a layer formed by applying and drying an anchor coat agent, and can improve the adhesion between adjacent layers. The anchor coating agent may be any resin having a heat resistance of 135°C or higher, such as vinyl. Examples of the anchor coating agent include those made of modified resin, epoxy resin, urethane resin, polyester resin, polyethyleneimine, and the like. Among the above, a curable anchor coating agent is particularly preferred which contains a polyacrylic or polymethacrylic resin (polyol) having two or more hydroxyl groups in one molecule as the base agent and an isocyanate compound as the curing agent. A silane coupling agent may also be used in combination, and nitrocellulose may also be used in combination to improve heat resistance. The thickness of the anchor coat layer is not particularly limited, but is preferably, for example, 0.05 μm or more and 1 μm or less.
[0129] <Functional layer> Examples of the functional layer include a layer made of a resin that has low adsorption of fragrance ingredients contained in the contents to be filled and packaged, has excellent aroma retention, and does not cause taste changes or unpleasant odors, and can be extruded, and a layer made of a light-shielding material (light-shielding layer).The functional layer may have barrier properties against oxygen gas, water vapor, etc.
[0130] Specific examples of the resin that can be used include polyacrylic resins, polymethacrylic resins, polyacrylonitrile resins, polymethacrylonitrile resins, polystyrene resins, polycarbonate resins, polyethylene terephthalate resins, or resins in which a portion of the ethylene component and / or terephthalate component thereof is copolymerized or modified with other di- or higher polyhydric alcohol components or dicarboxylic acid components, or polyester resins such as polyethylene naphthalate resins, polyamide resins, saponified ethylene-vinyl acetate copolymers, polyvinyl alcohol resins, polyvinyl chloride resins, polyvinylidene chloride resins, and other resins.
[0131] Among the above-mentioned resins, it is preferable to use a resin that has aroma retention and also has barrier properties against oxygen gas or water vapor, etc., and specifically, it is preferable to use a resin that is rich in aroma retention and barrier properties, such as a saponified ethylene-vinyl acetate copolymer, a polyamide resin, a polyacrylonitrile resin, or a polyester resin.
[0132] The light-shielding layer is a layer provided to prevent ultraviolet light and / or visible light from reaching the contents. The light-shielding layer can be formed using white ink mainly composed of titanium oxide or the like, black ink mainly composed of carbon black or the like, gray ink mainly composed of aluminum paste, colorant-colored resin film made light-shielding by adding pigments or dyes or the like, metal foil, metal vapor deposition film, or the like. As described above, when a metal foil such as an aluminum foil is used as the barrier layer, the barrier layer can also function as a light-shielding layer. These light-shielding materials can be used alone or in combination of two or more.
[0133] When white ink, black ink or gray ink is used, the thickness of the light-shielding layer is preferably 4 μm or more and 12 μm or less, and more preferably 5 μm or more and 9 μm or less. In the case of aluminum foil, the thickness is preferably 5 μm to 30 μm, in the case of a metal vapor deposition film, the thickness is preferably 50 Å to 3000 Å, more preferably 100 Å to 1000 Å, and in the case of a colorant-colored resin film, the thickness is preferably 5 μm to 300 μm, more preferably 10 μm to 100 μm.
[0134] <Reinforcement layer> The reinforcing layer is a layer that imparts mechanical strength, deformation resistance, drop impact resistance, pinhole resistance, heat resistance, airtightness, quality maintenance, workability, sanitation, and the like to the laminate. The reinforcing layer may be formed from any of an extrusion-formed or inflation-formed resin film, a resin-coated film, synthetic paper, and the like.
[0135] Specific examples of the resin contained in the reinforcing layer include low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, polypropylene, ethylene-propylene copolymer, ethylene-vinyl acetate copolymer, ionomer resin, ethylene-ethyl acrylate copolymer, ethylene-acrylic acid or methacrylic acid copolymer, methylpentene polymer, polybutene resin, polyvinyl chloride resin, polyvinyl acetate resin, polyvinylidene chloride resin, vinyl chloride-vinylidene chloride copolymer, poly(meth)acrylic resin, polyacrylonitrile resin, polystyrene resin, acrylonitrile-styrene copolymer (AS resin), acrylonitrile-butadiene-styrene copolymer (ABS resin), polyester resin, polyamide resin, polycarbonate resin, polyvinyl alcohol resin, saponified ethylene-vinyl acetate copolymer, fluorine resin, diene resin, polyacetal resin, polyurethane resin, cellulose, nitrocellulose, and other known resins.
[0136] In the present invention, it is preferable to use a polyester resin for the reinforcing layer. Examples of polyester resins include polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), polybutylene naphthalate (PBN), polytetramethylene terephthalate, and polycyclohexane dimethylene terephthalate (PCT).
[0137] The resin film may be either unstretched or uniaxially or biaxially stretched. The reinforcing layer may be provided with a vapor deposition film for the purpose of improving the barrier property, and may contain additives such as antioxidants, ultraviolet absorbers, light stabilizers, antistatic agents, antiblocking agents, flame retardants, crosslinking agents, and colorants, as long as the properties of the present invention are not impaired. The thickness of the reinforcing layer is not particularly limited, but is preferably 5 μm or more and 500 μm or less, and more preferably 10 μm or more and 200 μm or less.
[0138] <Method for producing oxygen-absorbing coated laminate> A method for producing an oxygen-absorbing coated laminate using the above-mentioned materials will be described below. The production method described below is an example and does not limit the present invention. The layers constituting the oxygen-absorbing coated laminate can be laminated by any method used in the production of ordinary packaging materials, such as wet lamination, dry lamination, solventless dry lamination, extrusion lamination, T-die coextrusion molding, coextrusion lamination, inflation molding, and the like. The oxygen-absorbing coated laminate of the present invention can also be subjected to secondary processing for the purpose of imparting surface functions such as chemical functions, electrical functions, magnetic functions, mechanical functions, friction / wear / lubrication functions, optical functions, thermal functions, and biocompatibility. Examples of secondary processing include embossing, painting, adhesion, printing, metallizing (plating, etc.), mechanical processing, surface treatment (antistatic treatment, corona discharge treatment, plasma treatment, photochromism treatment, physical vapor deposition, chemical vapor deposition, coating, etc.), etc. The laminate of the present invention can also be subjected to lamination (dry lamination and extrusion lamination), bag making, and other post-processing.
[0139] When the above lamination is performed, if necessary, the surface of each layer may be pretreated, for example, by corona treatment or ozone treatment. In addition, anchor coating agents such as isocyanate-based (urethane-based), polyethyleneimine-based, polybutadiene-based, and organic titanium-based agents may be used. Alternatively, an anchor coating agent such as a laminating adhesive, such as a polyurethane-based, polyacrylic-based, polyester-based, epoxy-based, polyvinyl acetate-based, cellulose-based, or other adhesive, can be used.
[0140] The substrate layer, oxygen barrier layer, and oxygen absorbing coating layer may be formed or stacked in any order. An example of a method for producing the oxygen-absorbing coated laminate will be described below. For example, when the oxygen-absorbing coated laminate has a layer structure of substrate layer / oxygen barrier layer / oxygen-absorbing coating layer, and the substrate layer / oxygen barrier layer is made of a resin film with an inorganic vapor deposition layer, the oxygen-absorbing coated laminate can be obtained by applying and drying an oxygen-absorbing coating agent to the inorganic vapor deposition layer surface of the resin film with an inorganic vapor deposition layer. For example, when the oxygen-absorbing coated laminate has a layer structure of substrate layer / oxygen barrier layer / oxygen-absorbing coating layer, and the substrate layer / oxygen barrier layer are made of barrier paper (layer structure: base paper / water vapor barrier resin layer / oxygen barrier resin layer), first, the surface of the barrier paper facing the oxygen barrier resin layer is subjected to a corona treatment, and then an oxygen-absorbing coating agent is applied to the corona-treated surface and dried to obtain the oxygen-absorbing coated laminate.
[0141] Furthermore, a heat sealing agent can be applied by part coating to the oxygen-absorbing coating layer surface of the oxygen-absorbing coating laminate obtained above and dried to obtain an oxygen-absorbing coating laminate having a layer structure of base layer / oxygen barrier layer / oxygen-absorbing coating layer / sealant layer. The oxygen-absorbing coated laminate obtained above may be subjected to an aging treatment, if necessary. In this manner, an oxygen-absorbing coated laminate can be obtained.
[0142] <Oxygen-absorbing coated packaging material> The oxygen absorbing coated packaging material is a packaging material made from an oxygen absorbing coated laminate. The oxygen-absorbing coated packaging material may further contain layers having various functions, if necessary.
[0143] <Oxygen-absorbing coated packaging> The oxygen-absorbing coated package is a package made from an oxygen-absorbing coated packaging material, and can be given added value by various shape designs and printing decorations. In the oxygen-absorbing coated package, the oxygen barrier layer is positioned outside the oxygen-absorbing coating layer.
[0144] In one embodiment, the oxygen-absorbing coated package of the present invention may be a pouch. A pouch can be made using less material than a bottle, and is effective in saving resources. Specific examples of pouch shapes include a basic flat pouch, a gusset-type pouch in which the bottom of the pouch spreads out, for example, into a square shape so that the pouch can stand on its own, a refill pouch, a retort pouch, a microwave pouch, a liquid sachet pouch, a bag-in-box pouch, an infusion bag pouch, a stick packaging pouch, a spouted pouch in which the spout is attached to the center or upper corner of the pouch, etc. Sealing by heat sealing can provide airtightness, and adding a zipper or spout can increase convenience in taking the contents in and out and in storage.
[0145] <Method of manufacturing oxygen-absorbing coated packaging> An oxygen-absorbing coated packaging bag, which is one embodiment of the oxygen-absorbing coated packaging body, can be formed, for example, by the following method. The example given below is merely one example of a method for producing the oxygen-absorbing coated packaging body of the present invention, and the present invention is not limited thereto. An oxygen-absorbing coated pouch, which is one embodiment of the oxygen-absorbing coated packaging bag, can be produced in various shapes, for example, by folding the oxygen-absorbing coated packaging material in half, or by preparing two sheets of the oxygen-absorbing coated packaging material, overlapping them with their sealant layer faces facing each other, and then heat-sealing the peripheral edges using a heat seal type, such as a side seal type, two-sided seal type, three-sided seal type, four-sided seal type, envelope seal type, grommet seal type (pillow seal type), pleated seal type, flat bottom seal type, square bottom seal type, or gusset type. In the above, the heat sealing can be performed by a known method such as bar sealing, rotary roll sealing, belt sealing, impulse sealing, high frequency sealing, ultrasonic sealing, flame sealing, etc.
[0146] The present invention will be described in more detail below with reference to examples and comparative examples. EXAMPLES
[0147] The present invention will be described in more detail with reference to the following examples and comparative examples, but the present invention is not limited to these examples.
[0148] <Raw materials> The main raw materials used in the examples are as follows: [Raw materials for oxygen absorbing compounds] Hydroxyl-terminated polyisoprene 1: Poly ip, manufactured by Idemitsu Kosan Co., Ltd. Number average molecular weight: 2500. Polycarbonate diol 1: Duranol T5651 manufactured by Asahi Kasei Chemicals Corporation. Number average molecular weight: 1000. · Oxygen absorbing compound 1: 3a,4,5,6,7,7a-hexahydro-4,7-methano-1H-inden-6-ol. - Oxidation-promoting catalyst solution 1: Octope AE, Hope Pharmaceutical Co., Ltd. 4% cobalt octylate in ethyl acetate. · Oxidation-promoting catalyst solution 2: Aceto-pe Mn(III) manufactured by Hope Pharmaceutical Co., Ltd. A 10% ethyl acetate solution of acetylacetone manganese(III), an oxidation-promoting catalyst. · General-purpose coating agent 1: Protouch White 077-0204, a special modified polyester resin paint manufactured by Rock Paint Co., Ltd. Solid content 49.5% by mass. General-purpose coating agent 2: Acrylic silicone resin paint manufactured by Rock Paint Co., Ltd., Crystal Rock UV Guard Clear, 159-0150. Solid content 47.2% by mass.
[0149] [Sealant layer] Heat sealant: Seikadyne 1900w, manufactured by Dainichi Seika Chemicals Co., Ltd. A water-based part coating agent containing EVA and chlorinated PP. [Base layer, oxygen barrier layer] · Transparent vapor-deposited PET film 1: IB-PET manufactured by Dai Nippon Printing Co., Ltd. One-sided transparent alumina vapor-deposited PET film. 12μm thick. Barrier paper 1: Shield Plus by Nippon Paper Industries Co., Ltd. Basis weight 66g / m 2The layer structure is base paper / water vapor barrier resin layer / oxygen barrier resin layer / protective resin layer. The basis weight of the base paper is 50g / m 2 The water vapor barrier resin layer is a coating layer containing kaolin, and the oxygen barrier layer contains polyvinyl alcohol as a water-soluble polymer.
[0150] <Preparation of raw material solutions> (Synthesis of polyol 1 and preparation of polyol solution 1) The following raw materials were added to a flask equipped with a nitrogen inlet tube, a stirrer, a rectification column, and a condenser, and a dehydration condensation reaction was carried out at an internal temperature of 180 to 200° C. with stirring. Ethylene glycol 70.0 parts by mass Neopentyl glycol 140.0 parts by mass 1,6-Hexanediol 190.0 parts by mass Isophthalic acid 300.0 parts by mass Terephthalic acid 300.0 parts by mass When the acid value of the solid content of the reaction liquid reached 15 mgKOH / g, the dehydration reaction was further allowed to proceed at 200 to 240° C. while blowing in nitrogen. When the acid value of the solid content of the reaction liquid became 10 mgKOH / g or less, the internal pressure was reduced to 30 Torr and the reaction was continued. When the acid value of the solid content of the reaction liquid became 0.1 mgKOH / g or less, the reaction was terminated and the liquid was cooled to room temperature to obtain Polyol 1. The number average molecular weight of the resulting polyester polyol, Polyol 1, was 8,000. Next, polyol 1 was dissolved in ethyl acetate to prepare a polyol solution 1 having a solid content of 60% by mass.
[0151] (Synthesis of polyol 2 and preparation of polyol solution 2) The following raw materials were charged into a flask equipped with a nitrogen inlet tube, a stirrer, and a condenser, and the mixture was heated with stirring to carry out a reflux reaction for 6 hours. Polycarbonate diol 1 100.0 parts by mass 1,6-Hexanediol 50.1 parts by mass Isophorone diisocyanate 118.5 parts by mass Ethyl acetate 138.0 parts by mass When it was confirmed by infrared absorption spectroscopy that the absorption of the isocyanate group had completely disappeared, the synthesis was terminated and the reaction mixture was cooled to obtain polyol 2. The number average molecular weight of the resulting urethane chain-extended polyester-polycarbonate polyol, polyol 2, was 8,000. Next, polyol 2 was dissolved in ethyl acetate to prepare a polyol solution having a solid content of 60% by mass.
[0152] (Synthesis of polyol 3 and preparation of polyol solution 3) The following raw materials were added to a flask equipped with a nitrogen inlet tube, a stirrer, a rectification column, and a condenser, and a dehydration condensation reaction was carried out at an internal temperature of 180 to 200° C. with stirring. Ethylene glycol 70.0 parts by mass Neopentyl glycol 140.0 parts by mass 1,6-Hexanediol 190.0 parts by mass Isophthalic acid 300.0 parts by mass Terephthalic acid 300.0 parts by mass When the acid value of the solid content of the reaction liquid reached 15 mgKOH / g, the dehydration reaction was further allowed to proceed at 200 to 240° C. while blowing in nitrogen. When the acid value of the solid content of the reaction liquid became 10 mgKOH / g or less, the internal pressure was reduced to 30 Torr and the reaction was continued. When the acid value of the solid content of the reaction liquid became 3 mgKOH / g or less, the reaction was terminated and the reaction liquid was cooled to room temperature, thereby obtaining polyol 3. The number average molecular weight of the resulting polyester polyol, Polyol 3, was 2,000. Next, polyol 3 was dissolved in ethyl acetate to prepare a polyol solution having a solid content of 60% by mass.
[0153] (Preparation of polyisocyanate solution 1) The following raw materials were added to a flask equipped with a nitrogen inlet tube, a stirrer, and a condenser and stirred to obtain a polyisocyanate solution 1 having a solid content of 60% by mass. Hexamethylene diisocyanate (buret form) 100.0 parts by mass Ethyl acetate 66.7 parts by mass
[0154] [Table 1]
[0155] <Synthesis of oxygen absorbing compound and preparation of oxygen absorbing compound solution> [Oxygen absorbing compound 2] First, the following raw materials were added to a flask equipped with a nitrogen inlet tube, a stirrer, and a condenser, and the mixture was reacted at an internal temperature of 80 to 90° C. for 8 hours with stirring. Oxygen absorbing compound 1 100.0 parts by mass Isophorone diisocyanate 74.0 parts by mass When it was confirmed that the absorption of the isocyanate group had completely disappeared in the infrared absorption spectrum, the synthesis was terminated and the mixture was cooled to obtain oxygen-absorbing compound 2. Then, the oxygen-absorbing compound 2 was dissolved in ethyl acetate to prepare an oxygen-absorbing compound solution 2 having a solid content of 80 mass %.
[0156] [Oxygen absorbing compound 3] First, the following raw materials were added to a flask equipped with a nitrogen inlet tube, a stirrer, and a condenser, and the mixture was reacted at an internal temperature of 80 to 90° C. for 8 hours with stirring. Oxygen absorbing compound 1 100.0 parts by mass Polyisocyanate solution 1 212.5 parts by weight When it was confirmed that the content of NCO groups in the solid content of the reaction liquid by the amine equivalent method reached approximately 0.64 mass %, the synthesis was terminated, the liquid was cooled, and the solvent was removed to obtain oxygen-absorbing compound 3. Then, the oxygen-absorbing compound 3 was dissolved in ethyl acetate to prepare an oxygen-absorbing compound solution 3 having a solid content of 60 mass %.
[0157] [Oxygen-absorbing compound 4] First, the following raw materials were added to a flask equipped with a nitrogen inlet tube, a stirrer, and a condenser, and the mixture was reacted at an internal temperature of 80 to 90° C. for 8 hours with stirring. Oxygen absorbing compound 1 100.0 parts by mass Polyol solution 1 2000.0 parts by mass Isophorone diisocyanate 111.2 parts by mass When it was confirmed that the absorption of the isocyanate group had completely disappeared in the infrared absorption spectrum, the synthesis was terminated, and the mixture was cooled and the solvent was removed to obtain oxygen-absorbing compound 4. Then, the oxygen-absorbing compound 4 was dissolved in ethyl acetate to prepare an oxygen-absorbing compound solution 4 having a solid content of 60 mass %.
[0158] [Oxygen absorbing compound 5] (same as NP-2497 oxygen absorbing compound 4 except polyol) First, the following raw materials were added to a flask equipped with a nitrogen inlet tube, a stirrer, and a condenser, and the mixture was reacted at an internal temperature of 80 to 90° C. for 8 hours with stirring. Oxygen absorbing compound 1 100.0 parts by mass Polyol solution 3 682.3 parts by mass Polyisocyanate solution 1 265.6 parts by mass When it was confirmed that the absorption of the isocyanate group had completely disappeared in the infrared absorption spectrum, the synthesis was terminated, and the mixture was cooled and the solvent was removed to obtain oxygen-absorbing compound 5. Then, the oxygen-absorbing compound 5 was dissolved in ethyl acetate to prepare an oxygen-absorbing compound solution 5 having a solid content of 60 mass %.
[0159] Table 2 shows the composition of the reaction solution used in synthesizing oxygen-absorbing compounds 2 to 5. Moreover, the charged compositions of oxygen-absorbing compound solutions 2 to 5 are summarized in Table 3.
[0160] [Table 2]
[0161] [Table 3]
[0162] <Preparation of oxygen-absorbing coating composition> (Preparation of oxygen-absorbing coating composition A1) The following raw materials were mixed at room temperature to obtain an oxygen-absorbing coating composition. Oxygen absorbing compound solution 2 100.0 parts by mass General-purpose coating agent 1 192.0 parts by weight Oxidation promoting catalyst solution 1 1.1 parts by mass
[0163] (Preparation of oxygen-absorbing coating compositions A2 to A9 and B1) According to the formulations in Tables 4 and 5, oxygen-absorbing coating compositions were obtained in the same manner as in the preparation of oxygen-absorbing coating composition A1.
[0164] [Table 4]
[0165] [Table 5]
[0166] The oxygen-absorbing coating composition prepared above was used to carry out the following examples, and an oxygen-absorbing coated laminate was produced and evaluated. [Example 1] On the inorganic vapor deposition layer surface of the transparent vapor deposition PET film 1, the oxygen absorbing coating agent A1 was applied in a dry amount of 5.0 g / m 2 The solution was applied and dried so as to form an oxygen absorbing coating layer. Next, the heat sealant 1 was applied to the surface of the oxygen absorbing coating layer in a part coat (sealed portion) and dried to form a sealant layer, thereby obtaining an oxygen absorbing coating laminate, which was then subjected to various evaluations. Layer structure: transparent vapor deposition PET film 1 (base layer: PET film (12 μm) / inorganic vapor deposition layer: transparent alumina) / oxygen absorbing coating layer (5.0 g / m 2 ) / sealant layer (part coat, 6μm)
[0167] [Examples 2 to 9, Comparative Examples 1 and 2] Except for replacing the oxygen-absorbing adhesive composition A1 in Example 1 with any of the oxygen-absorbing adhesive compositions A2 to A9, B1, or general-purpose coating agent 1 as described in Table 6, the same procedure as in Example 1 was carried out to obtain an oxygen-absorbing coated laminate, which was then evaluated in the same manner.
[0168] [Example 10] The same procedure as in Example 1 was repeated to obtain an oxygen-absorbing coated laminate, except that the transparent vapor-deposited PET film 1 for the base layer and oxygen barrier layer was replaced with barrier paper 1 and an oxygen-absorbing coating agent was laminated on the oxygen barrier side, and the laminate was evaluated in the same manner. Layer composition: Barrier paper 1 (66 g / m 2 , base paper / water vapor barrier resin layer / oxygen barrier resin layer / protective resin layer) / oxygen absorbing coating layer (5.0g / m 2 ) / sealant layer (part coat, 6μm)
[0169] [Example 11] An oxygen-absorbing coated laminate was obtained in the same manner as in Example 1, except that the sealant layer was not formed, and was evaluated in the same manner. Layer structure: transparent vapor deposition PET film 1 (base layer: PET film (12 μm) / inorganic vapor deposition layer: transparent alumina) / oxygen absorbing coating layer (5.0 g / m 2 )
[0170] [Comparative Example 3] An oxygen-absorbing coated laminate was obtained in the same manner as in Example 10, except that the oxygen-absorbing adhesive A1 was replaced with the general-purpose coating agent 1, and was evaluated in the same manner.
[0171] [Table 6]
[0172] <Summary of Results> The oxygen-absorbing coated laminates of all the Examples exhibited a balance between excellent blocking resistance, oxygen absorption and low odor. On the other hand, the laminates of the comparative examples showed poor results in any one of blocking resistance, oxygen absorption amount, and low odor property.
[0173] <Evaluation method>
[0174] [Oxygen absorption] An oxygen sensor chip (non-destructive oxygen sensor chip manufactured by Precision Sensing) and the oxygen-absorbing coat laminate prepared above were enclosed inside a glass bottle having a capacity of 106 cc. The oxygen concentration was measured immediately after sealing and after 14 days of storage in a thermostatic chamber at 25°C, and the amount of oxygen absorbed by the test film was calculated. The oxygen concentration was measured using a non-destructive oxygen concentration meter (FIBOX4 OXYGEN METER) manufactured by Presence.
[0175] <Odor> After measuring the amount of oxygen absorbed, the air inside the glass bottle was smelled and the odor was judged according to the following criteria. Note that the odor originating from the sealant layer was excluded from the judgment. Evaluation criteria: 0: Odorless 1: Faint odor 2: Weak odor 3: Moderate odor 4: Strong odor
[0176] [Blocking resistance] Two identical oxygen-absorbing coated laminates were prepared, stacked with opposite sides facing each other, and tested using a permanent deformation tester (constant load type) manufactured by Tester Sangyo Co., Ltd., with a load of 115 N applied and left to stand at 40°C for 24 hours to check for the presence or absence of blocking between the two oxygen-absorbing coated laminates. Evaluation criteria: ○: No blocking ×: Blocking present [Explanation of symbols]
[0177] 1: Oxygen-absorbing coated laminate, oxygen-absorbing coated packaging material 2: Base material layer 2a: Barrier paper 2b: Paper base layer 3: Oxygen barrier layer 3a: Water vapor barrier resin layer 3b: Oxygen barrier resin layer 4: Oxygen absorbing coating layer 5: Sealant layer
Claims
1. An oxygen absorbing coating laminate comprising at least a substrate layer, an oxygen barrier layer, and an oxygen absorbing coating layer, the oxygen barrier layer includes one or more selected from the group consisting of a metal foil, a resin film with an inorganic vapor deposition layer, a resin coat film or resin film made of an oxygen barrier resin, and a barrier paper; The barrier paper has a layer structure including at least a base paper and an oxygen barrier resin layer, and is laminated so that the oxygen barrier resin layer is located on the oxygen-absorbing coating layer side. The oxygen-absorbing coating layer is a layer formed from an oxygen-absorbing coating composition, The oxygen-absorbing coating composition contains at least an oxygen-absorbing compound and an oxidation-promoting catalyst, The oxygen absorbing compound has one or more unsaturated five-membered rings, any bond between the five carbon atoms constituting the unsaturated five-membered ring is a carbon-carbon double bond; A monovalent and / or divalent or higher electron-donating organic group 1 is bonded to the unsaturated five-membered ring, When the number of the unsaturated five-membered ring is one, the five-membered ring or the organic group 1 has a functional group having an active hydrogen or a group in which the active hydrogen of the functional group having an active hydrogen is substituted with a monovalent organic group 2, when there are two or more unsaturated five-membered rings, the unsaturated five-membered rings are bonded to each other via a divalent or higher organic group 2 which substitutes an active hydrogen of an active hydrogen group on each of the five-membered rings or the organic group 1, the unsaturated five-membered ring structure or the structure consisting of the unsaturated five-membered ring and organic group 1 is derived from one or more members selected from the group consisting of cyclopentadiene, dicyclopentadiene, norbornene, and derivatives thereof; The organic group 2 includes a structural portion derived from an isocyanate compound, or an isocyanate compound and a hydroxyl group-containing compound. Oxygen absorbing coated laminate.
2. The isocyanate compound is xylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, toluene diisocyanate, diphenylmethane One or more selected from the group consisting of diisocyanates and derivatives thereof; The oxygen-absorbing coated laminate according to claim 1 .
3. the hydroxyl group-containing compound is one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof; 3. The oxygen-absorbing coated laminate according to claim 1 or 2.
4. The organic group 2 does not have a crosslinkable functional group. The oxygen-absorbing coated laminate according to any one of claims 1 to 3.
5. The organic group 2 has one or more crosslinkable functional groups, the crosslinkable functional group is a hydroxyl group and / or an isocyanate group; The oxygen-absorbing coated laminate according to any one of claims 1 to 3.
6. The oxygen-absorbing compound contains one or more compounds selected from the group consisting of compounds represented by the following formulas (1) to (4): The oxygen-absorbing coated laminate according to any one of claims 1 to 3. 【Chemistry 1】 【Chemistry 2】 【Chemistry 3】 【Chemistry 4】 (In the formula, a to e are each a number of 1 or more, and R 1 , R 2 , R 3 Each of the above is an organic compound having one or more carbon atoms. It is a group containing at least an alkylene and / or phenylene structure, and further containing a structure derived from one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof.
7. The oxygen-absorbing compound contains a compound represented by the following formula (5): The oxygen-absorbing coated laminate according to any one of claims 1 to 3. 【Chemistry 5】 (In the formula, f is a number of 0 or more, and R 4 and R 5 Each of the above is an organic group having one or more carbon atoms, containing at least an alkylene and / or phenylene structure, and may further contain a structure derived from one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof.
8. The oxidation-promoting catalyst is a peroxide or a compound containing a cation of a transition metal. The oxygen-absorbing coated laminate according to any one of claims 1 to 7.
9. The compound containing a cation made of a transition metal is a metal soap made of a transition metal compound capable of releasing a cation or complex made of a transition metal and an anion or ligand made of a fatty acid. The oxygen-absorbing coated laminate according to claim 8 .
10. The oxygen-absorbing coating composition further contains a modifying agent, 10. The oxygen-absorbing coated laminate according to claim 1, wherein the modifying agent comprises an isocyanate compound and / or a hydroxyl group-containing compound.
11. The isocyanate compound is one or more selected from the group consisting of xylylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, and derivatives thereof. The oxygen-absorbing coated laminate according to claim 10.
12. the hydroxyl group-containing compound includes one or more selected from the group consisting of polyester polyols, poly(meth)acrylic acid ester polyols, polyalkylene ether diols, and urethane chain-extended polyols thereof, vinyl chloride-vinyl acetate copolymers, cellulose acetate-based resins, styrene-maleic acid ester-based copolymers, polyamide-based resins, and polyimide-based resins; The oxygen-absorbing coated laminate according to claim 10 or 11.
13. An oxygen-absorbing coated packaging material produced using the oxygen-absorbing coated laminate according to any one of claims 1 to 12.
14. An oxygen-absorbing coated package produced using the oxygen-absorbing coated packaging material according to claim 13, The oxygen barrier layer is a layer located outside the oxygen absorbing coating layer. Oxygen absorbing coated packaging.
Citation Information
Patent Citations
Automotive breathable film perfume and preparation method thereof
CN113355162A
Filter type dust collector
JP1978031265A
Laminating type magnetic core for magnetic head
JP1981071816A
Ion plating device of high efficiency utilizing magnetic field of magnet and coil
JP1983073770A
Paper laminate having barrier property and its production method
JP2003094574A
